Advances in ELISA-based detection of equine leptospirosis - Thayná Laner Cardoso; Daniela Rodriguero Wozeak; Isabel Ladeira Pereira; Laura Dias da Silva Ribeiro; Rogério Oliveira Rodrigues; Daiane Drawanz Hartwig (Brazilian Journal of Microbiology, 2026)

Sustainable route for the production of starch submicrocrystals: Effect of α-amylase combined with ohmic heating on A-, B-, and C-type starches - Raphael Lucas Jacinto Almeida; Daniela Sofia Rodrigues Martins; Francieli Colussi; Ricardo Nuno Correia Pereira; Hugo Miguel Lisboa Oliveira; José António Couto Teixeira; Everaldo Silvino dos Santos (Food Research International, 2026)

Functional trait variation of the endangered subshrub Noticastrum hatschbachii across contrasting coastal restinga microhabitats - Josiane Wolff-Coutinho; Makeli Garibotti Lusa; Beatriz Fernandes Torres; Ana Claudia Rodrigues; Fernanda Maria Cordeiro Oliveira; Paulo Emílio Lovato; Leonardo Khaoê Giovanetti; Daniela Ciccarelli (Flora, 2026)

Role of kaolinite epigenesis in ferruginous oolitic micronodule formation in Plinthosols from Central Brazil - Daniela Schievano de Campos; Thiago Tavares Vidoca; Raphael Rodrigues Brizzi; Hermes Dias Brito; Michele Ribeiro Ramos; Rodrigo Estevam Munhoz de Almeida; Pablo Vidal-Torrado (CATENA, 2026)

The hidden power of trees: Do local trees combat excessive body weight in Southern Europe? - Ana C. Lourenço; Helena G. Nogueira; Daniela Rodrigues; Augusta Gama; Aristides M. Machado-Rodrigues; Maria Raquel G. Silva; Cristina Padez (Urban Forestry & Urban Greening, 2026)

Textural and compositional domains as tools for reconstructing retrograde UHT metamorphism: Insights from sapphirine-bearing granulites of the Salvador–Esplanada–Boquim Belt, São Francisco Craton, Brazil - Daniela Leal Rodrigues; Renato Moraes; Jailma Santos Souza-Oliveira; André Klumb (Lithos, 2026)

Protected designation of origin in EU olive oils: Rethinking quality differentiation, regulatory frameworks and future challenges - Daniela Ruano; Nuno Rodrigues; José Alberto Pereira (Food Research International, 2026)

Micro-FTIR identifies osteodifferentiation markers in heterogeneous mesenchymal stem cell populations - João T.S. Martins; Clara Martins; João A. Rodrigues; Inês C.R. Graça; Daniela S. Bispo; Ana L.M. Batista de Carvalho; Brian J. Goodfellow; João F. Mano; Mariana B. Oliveira; Mariela M. Nolasco; Maria P.M. Marques; Paulo J.A. Ribeiro-Claro; et al. (Analytica Chimica Acta, 2026)

Kogia Records in Brazilian Equatorial and Southwestern Atlantic Oceans - Joao Pedro M. Mura; Raphael B. Machado; Yasmin P. Viana; Natalia Rodrigues‐Soares; Giovanne A. Ferreira; Larissa Kelmer L. Kascher; Barbara S. Silva; Lucia O. Alencar; Gabrieli M. Rodrigues; Franciele R. de Castro; Daniela F. Godoy; Jose L. Pizzorno; et al. (Marine Mammal Science, 2026)
The pygmy ( Kogia breviceps ) and dwarf ( Kogia sima ) sperm whales are cryptic cetaceans characterized by inconspicuous surfacing behavior, small group sizes, and deep‐diving habits, making visual detection particularly challenging. Here, we present the first broad‐scale passive acoustic monitoring (PAM) assessment of Kogia spp. occurrence along the Brazilian coast, spanning both the Equatorial Atlantic Ocean (EAO) and Southwestern Atlantic Ocean (SWAO). Across 25 survey campaigns, 504 survey days, and more than 6441 h of acoustic recordings, 94 acoustic detections were identified, predominantly within the Brazilian Equatorial Margin (BEM), resulting in substantially higher detection‐per‐unit‐effort values in the EAO than in the SWAO. Two rare visual‐acoustic encounters of Kogia sima were also documented, including one detection incorporated into the dataset. A total of 2796 echolocation clicks were analyzed, exhibiting the characteristic narrow‐band high‐frequency acoustic profile of Kogia spp. (mean peak frequency = 126.2 ± 3.8 kHz; mean −3 dB bandwidth = 4.7 ± 2.56 kHz; mean inter‐click interval = 141 ± 97 ms). Detections occurred across a broad bathymetric range (9–4411 m), and kernel density analyses revealed spatial heterogeneity in occurrence patterns, with recurrent detection areas concentrated within the BEM. Collectively, these findings demonstrate the effectiveness of PAM for studying elusive deep‐diving cetaceans and provide an important baseline for future ecological monitoring, impact assessment, and conservation efforts targeting Kogia spp. in the western Atlantic.

Temperature as a Co-stressor modulating the ecotoxicity of 3,4-dichloroaniline in Daphnia magna - Daniela Rebelo; Sara Cristina Antunes; Bárbara Maurício; Victor de Freitas; Raquel Nunes da Silva; Sara Rodrigues (Aquatic Toxicology, 2026)

Inclusion of microalga Dunaliella salina in the diet of laying hens: effects on egg quality and sensory traits - Obete Madacussengua; Cátia Falcão Martins; Ana Beatriz Rodrigues Tavares; Daniela Filipa Pires Carvalho; Ana Rita Mendes; Tiago Guerra; António Pagarete; Suzana Ferreira-Dias; Miguel Pedro Mourato; José António Mestre Prates; André Martinho de Almeida; Madalena Lordelo (Algal Research, 2026)

Integrative cytogenetic and molecular analyses in Hypostomus sertanejo reveal the lowest diploid number in the genus (Siluriformes: Loricariidae) - Daniela Rodrigues; Ligia Carla Balini; Bárbara Scorsim; Cláudio Henrique Zawadzki; Alessandra Valéria de Oliveira; Marcos Otávio Ribeiro; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes; Eliane Papa Ambrosio-Albuquerque; Luciana Andreia Borin-Carvalho (Biologia, 2026)
Expanding integrative cytogenetic and molecular analyses is essential for understanding the evolutionary dynamics of chromosome number variation in fishes. This study presents the first cytogenetic characterization of Hypostomus sertanejo , an endemic species native to the semi-arid Jaguaribe River basin in Northeastern Brazil. Cytogenetic analysis revealed a diploid number of 2n = 52, which is the lowest documented for the genus, with a karyotype composed of 22m + 8sm + 16st + 6a and a fundamental number of 98. This value aligns with the ancestral diploid number suggested for the tribe Hypostomini. Fluorescence in situ hybridization identified a single 18S rDNA site coinciding with the nucleolar organizer region, while 5S rDNA was localized to an interstitial position on a unique chromosome pair. Molecular analysis based on COI gene confirmed the identity of H. sertanejo and its distinction from closely related species. These results reveal a distinctive evolutionary trajectory for H. sertanejo relative to other Hypostomus species and highlight the importance of integrating data to elucidate diversification patterns in endemic fish lineages.

Influence of geographical origin on the sensory and volatile profiles of Portuguese monovarietal olive oils - Pedrina Rocha; Daniela Ruano; Nuno Ferreiro; Luísa L. Martins; Nuno Rodrigues (Food Research International, 2026)

Application of FT-IR spectroscopy using the IR Biotyper® for Leptospira: protocol optimization and first spectral insights - Amanda Maria Jesus Bertani; Elaine Santos Lima; Natalia da Cunha Nobrega; Marcelo Sansone; Juliana Alves Garcia; Daniela Leite; Gisele Oliveira de Souza; Tamires Santos de Arruda; Ricardo Polatto; Eliete Calo Romero; Tania Sueli de Andrade; Karoline Rodrigues Campos; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Thermal limits of estuarine amphipods and their implications for aquaculture production - Daniela P. Rodrigues; Luísa Marques; Joana Teixeira; João Ferreira; João P. Sousa; Rafael C. Duarte; Ricardo Calado (Marine Environmental Research, 2026)

Reproductive toxicity induced by a repeated 28-day oral exposure to a commercial mixture of the herbicides S-metolachlor and flumioxazin in male rats - Renata K. Carvalho; Diego S. Reis; Ana Luísa G. Santiago; Bruna M. Rodrigues; Jacqueline A. Leite; Walter D. Júnior; Virgínia Damin; Monica L. Andersen; Maingredy R. Souza; Paulo C. Ghedini; Hericles M. Campos; Daniela M. Silva; et al. (Chemico-Biological Interactions, 2026)

Preliminary Physicochemical Assessment of Aquaculture Effluents for Irrigation Reuse in the Brazilian Semi-Arid - Tereza Amelia Lopes Cizenando Guede Rocha; Rafael Oliveira Batista; Silvanete Severino da Silva; Stefeson Bezerra de Melo; Phâmella Kalliny Pereira Farias; Palloma Vitória Carlos de Oliveira; Francisco Éder Rodrigues de Oliveira; Daniela da Costa Leite Coelho; Luiz Fernando de Sousa Antunes; Antônio Gustavo de Luna Souto; Laio Ariel Leite de Paiva; Fagner Nogueira Ferreira (Water, Air, & Soil Pollution, 2026)
Aquaculture effluents are increasingly recognized as a strategic resource for agricultural water reuse, especially in semi-arid regions, where water scarcity and fertilizer costs intensify pressure on production systems. Within a circular economy framework, these effluents may simultaneously supply water and nutrients; however, their physicochemical composition must be carefully assessed, since excessive salt loading may impair soil quality and threaten long-term agricultural sustainability. This study performed a preliminary physicochemical assessment of raw and diluted aquaculture effluents to determine their potential for irrigation reuse in the Brazilian semi-arid, with emphasis on salinity, sodicity, ionic composition, nutrient-related parameters, and trace elements. The experiment was conducted at the Federal Rural University of the Semi-Arid (UFERSA), Mossoró, northeastern Brazil, from October 2022 to December 2023. Five treatments were evaluated: T1 (100% freshwater), T2 (75% freshwater + 25% effluent), T3 (50% freshwater + 50% effluent), T4 (25% freshwater + 75% effluent), and T5 (100% effluent). Samples were analyzed for pH, electrical conductivity (EC), major ions, nutrients, and trace elements, while sodium adsorption ratio, magnesium hazard, residual sodium carbonate, and hardness were also determined. Dilution with freshwater partially improved irrigation suitability but increasing effluent proportion intensified hydrochemical restrictions. Although effluents supplied relevant amounts of Ca 2+ , Mg 2+ , N, and P, reuse potential was mainly limited by salinity, particularly EC and Cl − , whereas sodicity remained secondary. Multivariate analysis identified EC, Ca 2+ , Mg 2+ , Cl⁻, HCO₃ − , P, SAR, Mn, Zn 2+ , and N as the main drivers of water quality variation, supporting irrigation reuse under controlled dilution, drainage, and continuous monitoring protocols. Graphical Abstract

Oil-in-water Emulsion as a Strategy for Taste Masking of Cannabinoid Extract - Juliana Feitoza Brasil; Luiza Aparecida Luna Silvério; Claudete da Costa-Oliveira; Leonardo Costalonga Rodrigues; Maria Helena Gonçalves; Leonardo Mathias Leidens; Carla Daniela Boeira; Jose Luiz Costa; Antonio Riul Junior; Priscila Gava Mazzola (AAPS PharmSciTech, 2026)

Influence of non-host aromatic plants on the survival and olfactory behavior of the African citrus psyllid, Trioza erytreae - Jaciley Bragança-Costa; Daniela Ruano; Nuno Rodrigues; Alberto Fereres; José Alberto Pereira; Isabel Rodrigues (Journal of Pest Science, 2026)
Trioza erytreae Del Guercio, 1918, commonly known as the African citrus psyllid, is one of the main vectors of Huanglongbing (citrus greening), the most destructive citrus disease worldwide. Currently, there is no effective treatment for HLB; therefore, management efforts primarily focus on controlling the insect vectors. This often involves the use of insecticides, which raises concerns about environmental impact and the development of insecticide resistance. This study evaluates the potential of five aromatic non-host plants commonly found in the Mediterranean basin, which overlap with regions of citrus production ( Cistus ladanifer , Rosmarinus officinalis , Foeniculum vulgare , Lavandula stoechas , and Thymus mastichina ) to influence the survival and olfactory behavior of T. erytreae . Although the psyllids were able to survive for several days on these non-host plants, survival was significantly lower compared to the citrus host ( Citrus limon ), with C. ladanifer having the most detrimental effect. Olfactory assays revealed that, in females, C. limon , C. ladanifer , and L. stoechas elicited significantly higher probabilities of attraction compared with R. officinalis and T. mastichina . In males, C. limon elicited a significantly higher probability of attraction than R. officinalis , T. mastichina , and L. stoechas . A total of 123 volatile organic compounds (VOCs) were identified across all plant species, of which 48 were found to be important for the olfactory response of T. erytreae . Among these, 19 VOCs were positively correlated with psyllid attraction, while 15 showed negative correlations, indicating a potential repellent or disruptive effect. These results suggest that specific VOCs emitted by aromatic non-host plants can modulate host-seeking behavior in T. erytreae , highlighting their potential application in the development of semiochemical-based, environmentally sustainable strategies for citrus pest management.

Differential expression of sperm capacitation-associated microRNAs in fresh and cryopreserved bovine semen - Laura Nataly Garcia-Oliveros; Alexandre da Rocha Bozzi; Thais de Oliveira Cardoso Silva; Fernanda Baatsch Nascimento; Thainara Rodrigues Oliveira; Maíra Bianchi Rodrigues Alves; Cibele Maria Prado Zinni; Yulizabeth Daniela Pinto Rojas; Juliano Coelho da Silveira; Felipe Perecin; Eneiva Carla Carvalho Celeghini (Animal Reproduction Science, 2026)

Tracing environmental contaminants in magellanic penguins: Legacy POPs and metabolic clearance of PAHs - Thales Henrique de Carvalho Storti; Antonio Derley de Sousa Pereira; Cristian Taboada Timoszczuk; Raphael de Lucca Marcello Jarcovis; Lígia Dias de Araujo; Daniela Alves Maia da Silva; Felipe Rodrigues dos Santos; Josilene da Silva; Satie Taniguchi; Rafael Andre Lourenço (Environmental Science and Pollution Research, 2026)
Persistent organic pollutants (POPs) are widespread contaminants that bioaccumulate in the food web, posing risks to wildlife, especially top predators. This study investigates the occurrence of POPs in liver tissues of 23 Magellanic Penguins ( Spheniscus magellanicus ) stranded along the Brazilian coast from June to September 2017. We analyzed concentrations of polychlorinated biphenyls (PCBs), organochlorine pesticides (DDTs, Drins, mirex, endosulfans), and hexachlorobenzene (HCB). POPs were detected in all samples. PCBs and DDTs showed the highest concentrations, with PCBs ranging from < LOD to 199.4 ng g −1 ww (mean: 57.2 ± 49.0 ng g −1 ww), showing a declining trend compared to previous reports. DDT metabolites, especially p,p′-DDE, remained persistent in the samples. HCB was found in 70% of the individuals but at lower levels than previously reported. Other pesticides were present at trace levels, consistent with their historical use in Brazil. No polycyclic aromatic hydrocarbons (PAHs) were detected, which we attribute to rapid metabolic clearance in penguins rather than lack of exposure. This emphasizes the species’ efficiency in eliminating these non-persistent compounds. Our findings highlight the continued presence of legacy POPs in the marine ecosystem and their bioaccumulation in seabirds. Although PCB levels appear to be decreasing, these pollutants still pose ecological risks. Monitoring efforts remain essential, especially considering the potential for re-exposure due to global distillation and melting of polar ice. This study contributes to understanding contaminant dynamics in the Southern Hemisphere and underscores the importance of long-term monitoring of marine wildlife.

Polysaccharide-mediated stabilization of bacterial nanocellulose dispersions: Experimental and molecular dynamics study - Ricardo Silva-Carvalho; Daniela Martins; Tarsila G. Castro; Ana Cristina Rodrigues; Bruna Costa; Paula Parreira; Artur Cavaco-Paulo; Fernando Dourado; M. Cristina L. Martins; Miguel Gama (Food Hydrocolloids, 2026)

Rifampicin Polymeric Nanoparticles for Tuberculosis: Molecular Dynamics, Physicochemical Characterization and Cytotoxicity - Lucas Marinho de Santana; Joandra Maísa da Silva Leite; Daniela Nadvorny; Antônia Carla de Jesus Oliveira; Raiza Raianne Luz Rodrigues; Klinger Antônio da Franca Rodrigues; Mônica Felts de La Roca Soares; José Lamartine Soares-Sobrinho (Journal of Pharmaceutical Innovation, 2026)
Tuberculosis infected 10.8 million people worldwide in 2023, resulting in 1.09 million deaths. Rifampicin (RIF) is one of the main drugs used in the treatment, but its low solubility and side effects, such as hepatotoxicity, limit its therapeutic efficacy. Polymeric nanoparticles (PNs) emerge as a promising strategy to optimize RIF delivery. This study aimed to develop RIF-PNs guided by molecular dynamics (MD), perform their physicochemical characterization and evaluate their in vitro cytotoxicity. MD allowed observing the molecular interactions between the components of the formulation and led to the formation of PNs. The PNs presented an average size of 177.0 ± 0.80 nm, polydispersity index of 0.094 ± 0.046, zeta potential of -15.0 ± 0.65 mV, encapsulation efficiency of 20.98% and drug loading of 2.29%, with colloidal stability maintained for up to 180 days. The physicochemical characterizations indicated the polymorphic form II of RIF, amorphous pattern of ethylcellulose (EC) and encapsulation of RIF in PN. Atomic force microscopy observed a spherical shape of the particles with a size of 38.4 ± 14.6 nm. RIF-EC-PN presented a sustained release profile with release of 20.65 ± 0.44% in 24 h and and the unencapsulated RIF demonstrated a release of 90.75% in 15 min. Cell viability was demonstrated in monkey renal epithelial cells (LLC-MK2). PNs showed favorable properties as RIF delivery systems. Graphical Abstract

Integrated analysis of the chemical, biological, and toxicological property stability in essential oils from fresh and dehydrated Ocimum gratissimum leaves - Thiago Silva de Almeida; Pollyne Borborema Almeida de Lima; Naiana Santos da Cruz Santana Neves; Jaqueline Rodrigues da Silva; Francildo dos Santos Silva; Elita de Sousa Santos; Rivânia Pereira dos Santos; Júlio César Ribeiro de Oliveira Farias de Aguiar; Daniela Maria do Amaral Ferraz Navarro; Maria Flaviana Bezerra Morais-Braga; James Correia de Melo (South African Journal of Botany, 2026)

Brazil’s climate leadership paradox: hosting COP30 amid domestic environmental rollbacks - Daniela Debone; Ronan Adler Tavella; Mariana Vieira da Costa; Eliane Seiko Maffi Yamada; Flavio Manoel Rodrigues da Silva Júnior; Sandra de Souza Hacon; Paulo Artaxo; Simone Georges El Khouri Miraglia (International Environmental Agreements: Politics, Law and Economics, 2026)

Coarse particulate matter air pollution in Porto Metropolitan area, Portugal: time series analysis, trends and implications for public policies - Simone Georges El Khouri Miraglia; Ronan Adler Tavella; Daniela Debone; Rui Moreira Barbosa; Flavio Manoel Rodrigues da Silva Júnior; Clara Lopes Ribeiro; Simone Morais; Marisa Alexandra Marques Freitas (Environmental Science and Pollution Research, 2026)
Air pollution remains a persistent environmental and public health concern in urban regions. This study presents a 22-year analysis (2001–2022) of coarse particulate matter (PM 10 ) concentrations across 15 monitoring stations in the Porto Metropolitan Area (PMA), Portugal. The stations, pre-classified by national authorities as traffic, background-urban, background-suburban, or industrial, were used to assess long-term temporal trends and spatial variability. Annual mean PM 10 concentrations were calculated and linear regression was applied to evaluate trends. Differences between station types were tested using statistical analysis. The results revealed consistent decline in PM 10 levels from the early 2000s to the mid-2010s, followed by stagnation or increases at several stations in the final years of the series. While higher concentrations were historically observed at traffic and industrial sites, no statistically significant differences in annual mean PM 10 concentrations were found between stations of different classifications or within classifications, even when comparing distinct time periods. This homogeneity suggests widespread regional exposure, likely driven by shared emission sources, atmospheric transport, and urban development patterns across the PMA. When compared to World Health Organization (WHO) air quality guidelines, exceedances were frequent and persistent. From 2001 to 2011, nearly all stations with valid data exceeded the 2005 guideline of 20 µg/m 3 . Between 2012 and 2020, the exceedances gradually decreased, although several stations still surpassed the guideline. However, under the 2021 WHO guideline (15 µg/m 3 ), all stations with valid data for 2021 and 2022 again exceeded the guideline. These findings highlight the need for integrated, long-term air quality policies. Clinical trial number: Not applicable.

Parasitoids, predators, or scavengers? On the nature of flesh fly (Diptera: Sarcophagidae: Sarcophaginae) interactions with eusocial wasps (Hymenoptera: Vespidae) in light of new findings in Brazil - Filipe Macedo Gudin; Sávio Cunha Costa; Daniela Alejandra Torres Garcia; André Rodrigues de Souza (Insectes Sociaux, 2026)
Nests of eusocial wasps (Hymenoptera: Vespidae) are dynamic ecosystems that host a diverse array of organisms with varied ecological roles. Among the most common associates are true flies (Diptera), whose larvae act as sarcosaprophages, predators, or parasitoids. While the interactions of many dipterans with eusocial wasps are known, the precise nature of relationships between Sarcophaginae flesh flies (Sarcophagidae) and eusocial wasps has been a subject of debate, with many authors interpreting them as parasitoids or predators of the wasp brood. We re-evaluated the evidence for Sarcophaginae-Vespidae interactions in light of a new record of Sarcophaga ( Neobellieria ) polistensis Hall, 1933 in a nest of Polistes simillimus Zikán, 1951 from Brazil. The new record is described, including illustrations of males and females of S. ( N. ) polistensis , with notes on the taxonomy, distribution, and diagnostic characters of the species. Furthermore, we present a comprehensive revision of all known Sarcophaginae-Vespidae records, providing a new perspective on the classification and evolution of the feeding habits of these flies. Based on our observations and a comprehensive review of the literature, we argue that Sarcophaginae-Vespidae interactions are best described as being sarcosaprophagous. While predation cannot be entirely discarded in the absence of detailed observations, there is currently no evidence to support parasitoidism in Sarcophaginae-Vespidae interactions.

Differential effects of adolescent fatty acid amide hydrolase and monoacylglycerol lipase inhibition on adolescent and adult behaviors in male rats - Mary K. Estes; Vishnu Guda; Emei Thompson; Daniela Rodrigues de Oliveira; David B. Nowak; Cecilia J. Hillard; John R. Mantsch (Psychopharmacology, 2026)

Greywater use in anaerobic digestion of cattle manure: Advancing biogas yield, energy efficiency, and digestate valorization for environmental sustainability in semi-arid regions - Daniela Silva Gomes Moreira do Valle; Marcélio Alves Teotônio; Jadde Milena Guedes Secundino; Tassia Cristina da Silva; Elisabete Albuquerque dos Santos Benvenuto; Allan Almeida Albuquerque; Bárbara Ribeiro Alves Alencar; Alexandre Nunes da Silva; Sergio Peres; Rejane Rodrigues da Costa e Carvalho; Emmanuel Damilano Dutra; Rômulo Simões Cezar Menezes (Science of The Total Environment, 2026)

Chemical composition and acaricidal activity of essential oils from Alpinia zerumbet, Bixa orellana, Mesosphaerum suaveolens and Syzygium cumini against Oligonychus punicae on clonal seedlings of Eucalyptus grandis - Adriele de Castro Ferreira; Rosenya Michely Cintra Filgueiras; Paulo Roberto Ramalho Silva; Izaias Santos Marques; Antonio José Cantanhede Filho; Bruno de Araújo Gomes; Edson Rodrigues Filho; Franciele Costa de Sousa; Eslane Reis Farias Mendes; Helane Cristina De Andrade Rodrigues Severo; Alyne Freire de Melo; Kamilla de Andrade Dutra; et al. (Crop Protection, 2026)

Demographic Parameters of Iberian Killer Whales Between 2011 and 2023 - Ruth Esteban; Pauline Gauffier; Alfredo López; Francisco J. Gil‐Vera; Jörn Selling; Lilian Haristoy; Rocio Espada Ruiz; Pierre Guibert; André Días; Alfredo Rodrigues; Alejandro Onrubia; Mario Morcillo; et al. (Marine Mammal Science, 2026)
The Iberian killer whale subpopulation was assessed as critically endangered (CR) by the IUCN red list of threatened species based on the available information until 2011 on its low abundance, high newborn mortality, and dependency on the endangered Atlantic bluefin tuna. The present study focuses on updating the subpopulation demographic parameters between 2011 and 2023. Data were based on photo‐identification and stranding records. Abundance, survival, reproductive rates, and population growth were estimated through mark‐recapture models. Stranding records were used to estimate body size and calving seasonality. Sightings of newborn calves were also used for assessing seasonality. From 2011 through 2023, 26 stranding records were obtained, and 18,554 ID‐images were examined. This subpopulation showed a stable abundance, with 37 individuals in 2023, still qualifying for the IUCN CR category under criteria D. Calf survival rate has increased compared to pre‐2011, while adult survival has decreased, particularly for females. Reproductive rates were low, with an estimated interbirth interval of 8.3 years. The overall population growth rate was apparently stable at 0.46%. Most births occurred in the summer and fall. Iberian killer whales are generally smaller than the average body length of other killer whale populations throughout the world. The study emphasizes the need for long‐term monitoring and highlights new potential threats from fishing activities and recent disruptive interactions with recreational boats. The future of the subpopulation depends on recruitment and survival of juveniles and effective female reproduction.

Why marine gammarids belong to the future portfolio of aquafeed ingredients - Ricardo Calado; Marta Carvalho; Luísa Marques; Daniela P. Rodrigues; João P. Sousa; Felisa Rey; Maria Rosário Domingues; Joana Filipa Fernandes; Ruben X. G. Silva; Diana Madeira; Arne M. Malzahn; Óscar Monroig; et al. (Frontiers in Marine Science, 2025)
The sustainable supply of n-3 long-chain polyunsaturated fatty acids ( n -3 LC-PUFA) remains a major challenge for global aquaculture. Although plant oils, microalgae, genetically modified crops, insects, krill, and fish by-products have been explored as alternative sources, none currently provides a stand-alone solution for meeting the growing demand of n -3 LC-PUFA in aquafeeds’ production. Here, we present marine gammarids as a potential complementary source of these fatty acids. Our Perspective article focuses on the nutritional attributes of marine gammarids, including their naturally high levels of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and considers their biological traits that support aquaculture practicality. We also examine the potential of marine gammarids for circular bioeconomy applications through trophic upgrading of low-value side streams. While evidence from feeding trials is limited, preliminary data suggest marine gammarids may maintain their high EPA and DHA content even when fed on low-quality diets. Critical research priorities include developing scalable production systems, optimising feed formulations, evaluating performance across key aquaculture species, and assessing ecological and operational feasibility. This Perspective also highlights the potential of marine gammarids to contribute to a diversified and resilient aquafeed portfolio. Although they are unlikely to replace fish meal or fish oil entirely, marine gammarids may serve as a strategic complementary ingredient.

Excitable temperament impairs oocyte quality and in vitro embryo production efficiency in Nellore donors - Samuel Rodrigues Bonamichi do Couto; Nicolas Moreira Piedras Monnerat Caparelli; Thiago Souza Vieira; Daniela Cristina Rocha de Freitas; Mateus Gonçalves Costa; Mellyssa Sad Rodrigues Gomes; João Paulo Nascimento Andrade; Rondineli Pavezzi Barbero; Felipe Zandonadi Brandão; Marco Roberto Bourg de Mello (Livestock Science, 2025)

The dynamic of rare earth elements in the context of multiple bauxitization cycles: Evidence in the Southern Espinhaço Range (Southeastern Brazil) - Daniela Schievano de Campos; Thiago Tavares Vidoca do Nascimento; Ana Paula Dechen Rodrigues; Pablo Vidal-Torrado (Journal of South American Earth Sciences, 2025)

Biodegradation assessment of polymer-based films by bacterial species in the marine environment and its correlation with microplastic production and toxicity - Márcia Priscila Porto dos Santos; Natália de Albuquerque Vita de Abreu; Franciele Saorin; Tarcisio Camlofski; William Alves; Desiree Schuck; Camila Suliani Raota; Samara Letiele dos Santos; Letícia Steckel; Daniela Rodrigues Araujo; Wanessa Ramsdorf; Felipe Vannucchi de Camargo; et al. (Journal of Hazardous Materials, 2025)

Iron ore Tailling-enriched biochar for carbon improvement in coarse textured soils - Bernardo Amorim da Silva; Ivan Francisco de Souza; Vanessa de Barros Tostes Pereira; Fabiane Carvalho Ballotin; Anifo Soares Mamudo Ibraimo; Sandro Lucio Silva Moreira; Edson Marcio Mattiello; Daniela Cristina Costa; Rafael da Silva Teixeira; Igor Rodrigues de Assis; João José de Miranda Milagres; João Pedro de Oliveira Gomes; et al. (Biomass and Bioenergy, 2025)

Boron excess in Alternanthera tenella Colla under in vitro conditions: tolerance and potential for supplementation in plants - Marcel Merlo Mendes; Julia Felipe Miranda; Lívia Batista das Neves; João Paulo Rodrigues Martins; Ana Caroline Pariz Rocha; Daniela Cassol; Andreia Barcelos Passos Lima Gontijo; Antelmo Ralph Falqueto (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)
Boron (B) plays a crucial role in plant physiological processes, and imbalances in its supply can markedly affect plant morphophysiology. This study evaluated the effects of a B concentration gradient on the growth and morphophysiological responses of Alternanthera tenella under in vitro conditions. Stem segments were cultured on media supplemented with different B concentrations (0, 125, 250, 500, 750, 1000, and 2000 µM) for 30 days. Growth traits, anatomical features, nutrient accumulation, photosynthetic pigment content, and photosystem II (PSII) performance were assessed. Increasing B availability enhanced Mg and S accumulation, while the thickness of root vessel elements increased progressively up to 750 µM B. Tissues associated with nutrient transport exhibited improved functionality, indicating more efficient translocation from roots to shoots under adequate B supply. Photosynthetic pigment content and PSII parameters were also highest at 750 µM B. The tolerance index remained above 68% across all treatments, demonstrating that A. tenella is tolerant to elevated B levels. However, excessive B concentrations (≥ 1000 µM) induced physiological disturbances and PSII structural damage, likely associated with pigment reduction. Anatomical adjustments observed in plants exposed to high B concentrations may represent adaptive mechanisms limiting further B uptake. In addition, the study suggests that 750 µM B is recommended to enhance its morphophysiological performance under in vitro culture.

Under pressure: Daphnia magna’s responses to 4-chloroaniline exposure and climate-induced temperature rise - Daniela Rebelo; Sara C. Antunes; Sara Rodrigues (Environmental Science and Pollution Research, 2025)

Advancing regional satellite-based assessment of phytoplankton size structure in a subtropical Bight - Andréa de Lima Oliveira; Natália Rudorff; Shubha Sathyendranath; Fabio Dall Cortivo; Silvana Vianna Rodrigues; Daniela Sudatti; Luciano Felício Fernandes; Frederico Brandini; Milton Kampel (International Journal of Remote Sensing, 2025)

Characterization of genital system inflammatory response in female dogs naturally infected with Leishmania infantum* - Paulo Henrique Leal Bertolo; Maria Eduarda Bastos Andrade Moutinho da Conceição; Pamela Rodrigues Reina Moreira; Beatriz Cristiane Mioto; Rafael Rocha Mello Emboaba da Costa; Fernanda Ramalho Ramos; Bethânia Almeida Gouveia; Maricy Apparíccio Ferreira; Daniela Bernadete Rozza; Rosemeri de Oliveira Vasconcelos (Veterinary Immunology and Immunopathology, 2025)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

Oxidative analysis, clinical-laboratory parameters, and quality of life in treatment associated with ozone therapy in female dogs with mammary tumors - Viviane Abreu Pedreira de Oliveira; Marcela Próspero Rodrigues Pinto; Daniela Farias Larangeira; Laís Pereira Silva; Vitor de Moraes Pina de Carvalho; Gisele André Baptista Canuto; Hanna Carvalho de Sá; Gabriel Rodrigues Menezes; Karine Araújo Damasceno; Stella Maria Barrouin-Melo; Alessandra Estrela-Lima (Research in Veterinary Science, 2025)

Behavioral, regenerative, and reproductive responses of Girardia tigrina to imidacloprid exposure - Aline Arantes de Oliveira; Thays Millena Alves Pedroso; Andreia C. M. Rodrigues; Daniela de Melo e Silva; Renato Almeida Sarmento; Suzana Maria Loures de Oliveira Marcionílio; Hellem Victoria Ribeiro dos Santos; Aline Silvestre Pereira Dornelas; Althiéris de Souza Saraiva (Ecotoxicology, 2025)

Impact of Climate Change-Mediated Tragedies: An Account of Extreme Rainfall Event in Rio Grande do Sul, Brazil - Daniela Debone; Ronan Adler Tavella; Arnaldo Lopes Colombo; Ana Cristina Gales; Flávio Manoel Rodrigues da Silva Júnior; Simone Georges El Khouri Miraglia (Anthropocene Science, 2025)

Corrigendum to “Evaluation of the toxic and genotoxic effects of exposure of Drosophila melanogaster to the glutathione-capped AgIn5Se8@ZnS nanocrystals” [Chemosphere, (2025), vol. 381, pages 144482] - Antônio Marcos de Oliveira dos Santos; Danilo Gustavo Rodrigues Silva; Maria Gislaine Pereira; Adrielle Rodrigues Costa; Claudia Rohde; Camila Caroline Lopes Arruda; Antônia Eliene Duarte; Lizandra Ferraz da Silva; Denilson Vasconcelos Freitas; Marcelo Navarro; Maríndia Deprá; Daniela Maria do Amaral Ferraz Navarro; et al. (Chemosphere, 2025)

Whey protein and probiotic supplementation ameliorates DSS-induced colitis in mice - Amanda Ascanio; Jaqueline Cristina Galiardo; Eliane Vale da Silva; José Antônio Sampaio Zuanon; Luis Carlos Spolidorio; Letícia de Aquino Penteado; Priscila Marques Firmiano Dalle Piagge; José Fernando Rinaldi de Alvarenga; Alexandra Ivo de Medeiros; Daniel Rodrigues Cardoso; Daniela Cardoso Umbelino Cavallini (International Dairy Journal, 2025)

Baru (Dipteryx alata Vog.) by-product following gastrointestinal digestion: bioaccessibility, antioxidant capacity and in vitro effects on inflammatory response of phenolic compounds - Daniela Canuto Fernandes; José Rodrigues do Carmo Neto; Amanda de Oliveira Matos; Marcos dos Santos Lima; Helioswilton Sales-Campos; Maria Margareth Veloso Naves (Food Research International, 2025)

Exploring In Vitro Mesenchymal Stem Cell Osteodifferentiation via Vibrational Microspectroscopy: A Review - Daniela S. Bispo; Inês C. R. Graça; João A. Rodrigues; João T. S. Martins; Mariela M. Nolasco; Maria P. M. Marques; Helena I. S. Nogueira; João F. Mano; Mariana B. Oliveira; Paulo J. A. Ribeiro-Claro; Ana M. Gil (Stem Cell Reviews and Reports, 2025)
The application of vibrational microspectroscopy to the study of in vitro mesenchymal stem cells (MSC) osteogenic differentiation is a promising approach towards the understanding of the molecular processes involved in bone fabrication. Both infrared (IR) and Raman microspectroscopies have been applied, with a clear predominance of the latter. Bone marrow MSC have been the target of most studies, followed by those originating from dental/oral and adipose tissues. Interests have increasingly addressed single cell and extracellular matrix characterization at the molecular level. Most studies have focused on the characteristics and maturity of time-course mineralization, attempting to localize mineral aggregates formed onto the evolving collagen strands. Some reports have focused on time-dependent changes in protein structure and other components of extracellular matrix components. Besides spectral band examination through position, linewidth and shape, selected band ratios have proved largely informative to assess mineral species evolution and mineral-to-organic matrix interactions over time. The increasing use of multivariate analysis (or chemometrics) and machine learning strategies to detect finer spectral variations is evident, as is the promise of more recent IR and Raman variations to provide higher sensitivity and spatial resolution conditions. The label-free non-invasive nature of vibrational microspectroscopy makes it particularly promising for rapid and effective selection of suitable MSC donors, to support scale-up procedures for translation to the clinic. Some of the challenges to be faced are briefly discussed. Graphical Abstract

Effects of the inclusion of a rumen-protected B-vitamin blend and hydroxy trace minerals in the diets of confined Nellore cattle on performance and cecal and ruminal histology - Maria Carolina Gonçalves de Arruda; Rodrigo de Nazaré Santos Torres; Daniela Bernadete Rozza; Luis Arthur Loyola Chardulo; Welder Angelo Baldassini; Rogério Abdallah Curi; Guilherme Luis Pereira; Iasmin Myrele Santos Calaça de Farias; Marco Aurélio Porcionato; Otávio Rodrigues Machado Neto (Animal Feed Science and Technology, 2025)

Investigation of Cereus jamacaru DC. cladode extract for chemical composition and effects against pathogenic bacteria and Aedes aegypti L. larvae - Júlia Maria Rodrigues Guimarães; Lucas Gabriel Pita dos Santos; Alex Michel Silva Araújo; Welton Aaron de Almeida; Lidiane Quérolin Macena da Silva; Júlio César Ribeiro de Oliveira Farias de Aguiar; Emerson de Oliveira Silva; Isabella Coimbra Vila Nova; Ana Beatriz Sotero Siqueira; Maria Tereza dos Santos Correia; Márcia Vanusa da Silva; Rômulo Carlos Dantas da Cruz; et al. (South African Journal of Botany, 2025)

Nitrofuran (E)-N’-((5-nitrofuran-2-yl)methylene)furan-2-carbohydrazide: drug candidate for the treatment of visceral toxocariasis - Débora Carvalho Rodrigues; Andrezza Medeiros Faria; Carolina Netto de Oliveira da Cunha; Victória Pires Panassolo; Lourdes Helena Rodrigues Martins; Thais Cristina Mendonça Nogueira; Marcus Vinícius Nora de Souza; Márcia Cristiane Feltrin Dias de Souza; Lívia Silveira Munhoz; Luciana Farias da Costa de Avila; Daniela Fernandes Ramos; Carlos James Scaini (Medicinal Chemistry Research, 2025)

Changes in community composition and functional diversity of European bats under climate change - Penelope C. Fialas; Luca Santini; Danilo Russo; Francisco Amorim; Hugo Rebelo; Roberto Novella‐Fernandez; Francisco Marques; Adi Domer; Adriana Vella; Adriano Martinoli; Aleksandra Figurek; Asaf Tsoar; et al. (Conservation Biology, 2025)
Climate change is predicted to drive geographical range shifts that will result in changes in species diversity and functional composition and have potential repercussions for ecosystem functioning. However, the effect of these changes on species composition and functional diversity (FD) remains unclear, especially for mammals, specifically bats. We used species distribution models and a comprehensive ecological and morphometrical trait database to estimate how projected future climate and land‐use changes could influence the distribution, composition, and FD of the European bat community. Future bat assemblages were predicted to undergo substantial shifts in geographic range and trait structure. Range suitability decreased substantially in southern Europe and increased in northern latitudes. Our findings highlight the potential for climate change to drive shifts in bat FD, which has implications for ecosystem function and resilience at a continental scale. It is important to incorporate FD in conservation strategies. These efforts should target species with key functional traits predicted to be lost and areas expected to experience losses in FD. Conservation strategies should include habitat and roost protection, enhancing landscape connectivity, and international monitoring to preserve bat populations and their ecosystem services.

Fatty acid profile of Gammarus locusta newly hatched offspring from the wild and from adults farmed on mono-specific macroalgal diets - João P. Sousa; Luísa Marques; Daniela P. Rodrigues; Felisa Rey; Manuel Albuquerque; Maria Rosário M. Domingues; Rafael C. Duarte; Ricardo Calado (Frontiers in Marine Science, 2025)
The accelerated growth of marine aquaculture targeting species that require formulated aquafeeds creates a pressing need to find new sustainable ingredients and additives that can secure a premium farming performance, as well as the nutritional value of farmed species. Marine gammarid amphipods can be an excellent source of essential fatty acids (FA), namely, long-chain n -3 polyunsaturated FA (LC-PUFA). However, their potential contribution to aquaculture feeds remains largely unexplored. The present work evaluated the effect of five mono-specific macroalgal diets ( Ulva sp., Fucus sp., Laminaria sp., Gracilaria sp., and Chondrus sp.) on the FA composition of the offspring of Gammarus locusta fed on these macroalgae and compared it with the offspring of wild conspecifics. Results revealed that offspring from wild G. locusta showed the highest amount of PUFA (4.95 ± 0.31 μg mg -1 DW), as well as essential FA, namely eicosapentaenoic acid (EPA, 20:5 n -3) (2.49 ± 0.21 μg mg -1 DW) and docosahexaenoic acid (DHA, 22:6 n -3) (0.87 ± 0.16 μg mg -1 DW). The treatment with the highest amount of PUFA and EPA was the one using Fucus sp. as a mono-specific macroalgal diet (4.46 ± 0.31 μg mg -1 DW and 2.42 ± 0.24 μg mg -1 DW, respectively). The best levels of DHA in offspring were recorded for specimens feeding on Chondrus sp. (0.56 ± 0.10 μg mg -1 DW). Significant differences in the abundance of stearic acid (18:0) and DHA were observed between the offspring of adults fed algal-based diets and those from the wild. These findings suggest that G. locusta selectively conserves and directly or indirectly biosynthesises essential FA for growth and reproduction, particularly LC-PUFA. Overall, G. locusta can perform a trophic upgrade of its diet, making this gammarid amphipod a promising additive for the formulation of high-quality aquafeeds supplying LC-PUFA.

Evaluation of the toxic and genotoxic effects of exposure of Drosophila melanogaster to the glutathione-capped AgIn5Se8@ZnS nanocrystals - Antônio Marcos de Oliveira dos Santos; Danilo Gustavo Rodrigues Silva; Maria Gislaine Pereira; Adrielle Rodrigues Costa; Claudia Rohde; Camila Caroline Lopes Arruda; Antônia Eliene Duarte; Lizandra Ferraz da Silva; Denilson Vasconcelos Freitas; Marcelo Navarro; Maríndia Deprá; Daniela Maria do Amaral Ferraz Navarro; et al. (Chemosphere, 2025)

Evaluating dermal toxicity of the flame retardant aluminum diethylphosphinate by in silico-in vitro testing strategy - Enzo Zini Moreira Silva; Ana Carolina Rodrigues; Ana Flávia Kohler; Juliana Varella Cruz; Karin Braun Prado; Daniela Fiori Gradia; Danielle Palma de Oliveira; Cynthia Bomfim Pestana; Daniela Morais Leme (Chemosphere, 2025)

Targeted metabolomics of phenolic and volatile compounds during the fermentation of a potential probiotic tofu whey beverage - Mariana Fensterseifer Fabricio; Luana Schmidt; Paula Daniela Helfenstein Rother; Paula Rossini Augusti; Fernanda Candido; Roger Wagner; Michel José Anzanello; Eliseu Rodrigues; Marco Antônio Záchia Ayub (Food Chemistry, 2025)

Cytotoxic activity, phenolic content, and fatty acid of brown algae from tropical reefs - Samara Rodrigues; Elizabeth Fernanda de Oliveira Borba; Marllyn Marques da Silva; Fábio Henrique Galdino dos Santos; Noemia Pereira da Silva Santos; Terezinha Gonçalves da Silva; Fungyi Chow; Daniela Maria do Amaral Ferraz Navarro; Emerson Peter da Silva Falcão; Sonia Maria Barreto Pereira (Brazilian Journal of Botany, 2025)
New cancer therapies development is a huge demand. This research evaluated cytotoxic activity against normal and cancer cells of brown algae (Dictyotales) extracts with high antioxidant activity. Canistrocarpus cervicornis , Dictyopteris delicatula and Lobophora variegata extracts from two beaches of Pernambuco were obtained by two serial maceration method: 1° Extraction—dichloromethane and methanol (2:1 v/v) and subsequently water at 60 °C; 2° Extraction—dichloromethane and methanol (2:1 v/v), subsequently ethanol and finally water at 80 °C. Phenolic compounds and cytotoxicity against normal cell lines L-929 (murine fibroblast), PBMC (human peripheral blood mononuclear cells) and J774A1 (mouse macrophages), and cancer cell lines P815 (murine mastocytoma), S-180 (murine Sarcoma), NCI-H292 (human lung mucoepidermoid carcinoma), HCT-116 (human colorectal carcinoma), JUKART (human T cell leukaemia) and MCF-7 (human breast adenocarcinoma) were assessed. Only for L-929 strain, among normal cells, extracts presented cytotoxicity. Organic extracts showed moderate to high cytotoxic activity against P815, MCF-7 and HCT-116 cancer cell lines. Organic extract L. variegata Jaguaribe 2° Extraction exhibited the best cytotoxic activity with high IC 50 values (28–35 µg/mL). Thus, we evaluate its acids profile that showed important polyunsaturated fatty acids and carboxylic acid, such as arachidonic acid and cinnamic acid that is being reported to L. variegata for the first time. Various research demonstrated the anticancer activity of this substance. Therefore, the high cytotoxic activity of our most active extract could be due to the presence of fatty acids and carboxylic acid, acting synergically, including cinnamic acid. These results encourage macroalgae use as an anticancer metabolites source for human therapies.

A population under smoke: fire events trigger severe air pollution in Portugal - Simone Georges El Khouri Miraglia; Daniela Debone; Clara Lopes Ribeiro; Rui Moreira Barbosa; Ronan Adler Tavella; Flavio Manoel Rodrigues da Silva-Júnior; Manuela Vieira da Silva; Marisa Alexandra Marques Freitas (Environmental Science and Pollution Research, 2025)

Optimizing bacterial nanocellulose production from eucalyptus bark: A circular approach to wastewater management and resource recovery - Ana Cristina Rodrigues; Daniela Martins; M. Salomé Duarte; Ricardo Silva-Carvalho; Susana Marques; Ana Júlia Cavaleiro; Miguel Gama; Fernando Dourado (Journal of Environmental Chemical Engineering, 2025)

Toxicity of essential oils on Callosobruchus maculatus (Fabr., 1775) in grains of Vigna unguiculata - Ozael David Valério da Silva; Paulo Roberto Ramalho Silva; Leticia Rodrigues da Silva; Rodrigo de Carvalho Brito; Kamilla de Andrade Dutra; Daniela Maria do Amaral Ferraz Navarro; Douglas Rafael e Silva Barbosa; Solange Maria de França (Journal of Plant Diseases and Protection, 2025)

Coastal natural products: a review applied to antimycobacterial activity - Rodolfo Moreira Baptista; Marcos Alaniz Rodrigues; Fabio Roselet; César Serra Bonifácio Costa; Pedro Eduardo Almeida da Silva; Daniela Fernandes Ramos (Natural Product Research, 2025)

Retraction notice to “The exposure in ovo of embryos belonging to Amazonian turtle species Podocnemis expansa (Testudines) to commercial glyphosate and fipronil formulations impairs their growth and changes their skeletal development” [Sci. Total Environ. 842 (2022) 156709] - Juliana dos Santos Mendonça; Líria Queiroz Luz Hirano; André Luiz Quagliatto Santos; Daniela de Melo e Silva; Carolina de Castro Pereira; Matheus Santos Costa; Phâmella Neres de Lima; Amanda Pereira da Costa Araújo; Guilherme Malafaia; Isabela Sayuri Ambrósio; Lais de Moura Bife Castilho; Allyson Leandro Rodrigues dos Santos; et al. (Science of The Total Environment, 2025)

Visual soil assessment as an early indicator of soil quality in the caatinga dry tropical forest under varying degrees of disturbance in the Brazilian semiarid region - Wicliton Wagner de Oliveira Lima; Eulene Francisco da Silva; Diana Ferreira de Freitas; Jeane Cruz Portela; Lunara Gleika da Silva Rêgo; Daniela da Costa Leite Coelho; Eveline de Almeida Ferreira; Joaquim Emanuel Fernandes Gondim; Luiz Fernando de Sousa Antunes; Francisco Éder Rodrigues de Oliveira; Yara de Almeida Araújo; Marx Lima da Cunha; et al. (Science of The Total Environment, 2025)

Phytoplankton size structure in a subtropical area from ocean colour and its applications - Andréa de Lima Oliveira; Natália Rudorff; Shubha Sathyendranath; Fabio Dall Cortivo; Silvana Vianna Rodrigues; Daniela Sudatti; Milton Kampel (Journal of Marine Systems, 2025)

Prospecting the Functional Potential of Bacillus altitudinis 1.4 Isolated from Sediment in Association with Bradyrhizobium japonicum - Priscila Ribeiro Jankoski; Evelise Bach; Daniela Ritiele Quadros Bald; Luciane Maria Pereira Passaglia; Joseane Biso de Carvalho; Rafael Rodrigues de Oliveira; Wellington Pine Omori; Amanda de Souza da Motta (Current Microbiology, 2025)

Understanding the effects of Bothrops erythromelas and Bothrops leucurus venoms on human blood coagulation - Eduardo Oliveira Venancio de Lima; Lídia Jorge Tasima; Daniela Miki Hatakeyama; Maria Amélia Farias Rodrigues; Caroline Serino-Silva; Daniel Rodrigues Stuginski; Giovanni Perez Machado da Silveira; Benedito Carlos Prezoto; Kathleen Fernandes Grego; Sávio Stefanini Sant’Anna; Anita Mitico Tanaka-Azevedo; Karen de Morais-Zani (Toxicon, 2025)

The Ataxia-telangiectasia mutated (ATM) is the most important gene for repairing the DNA in Myelodysplastic Neoplasm - Ronald Feitosa Pinheiro; João Vitor Caetano Goes; Leticia Rodrigues Sampaio; Roberta Taiane Germano de Oliveira; Sheila Coelho Soares Lima; Cristiana Libardi Miranda Furtado; Daniela de Paula Borges; Marilia Braga Costa; Cristiane da Silva Monte; Natalia Feitosa Minete; Silvia Maria Meira Magalhães; Howard Lopes Ribeiro Junior (DNA Repair, 2025)

Optical immunosensor panel using quantum dot-antibody conjugates for highly sensitive detection of carbohydrate antigen 19–9 (CA19-9) - Daniela Oliveira; Pedro Oliveira; Ana Xu; Eduarda Rodrigues; Susana G. Guerreiro; Rafael C. Castro; David S.M. Ribeiro; João L.M. Santos; Ana Margarida L. Piloto (Analytica Chimica Acta, 2025)

Spatial distribution and geochemical background of quartzitic and ferruginous rupestrian field soils - Daniela Arcanjo Paiola Ferreira; Mariangela Garcia Praça Leite; Maria Cristina Teixeira Braga Messias; Maria Augusta Gonçalves Fujaco; Eduardo Duarte Marques; Lucas Mardones Gaião; Alessandra Rodrigues Kozovits (CATENA, 2024)

Simulated climate change and atrazine contamination can synergistically impair zebrafish testicular function - Victor Ventura de Souza; Davidson Peruci Moreira; Susana Braz-Mota; Wanderson Valente; Gustavo Caldeira Cotta; Maira da Silva Rodrigues; Rafael Henrique Nóbrega; Rebeca Dias Serafim Corrêa; Daniela Chemin de Melo Hoyos; Eduardo Antônio Sanches; Adalberto Luís Val; Samyra Maria dos Santos Nassif Lacerda (Science of The Total Environment, 2024)

Evaluation of operational parameters and technology readiness for enhanced management of oilfield produced water treated by ozonation - Sabryna Isabelly Giordani da Costa; Silvio Edegar Weschenfelder; Maria Alice Prado Cechinel; João Vítor R. Fuck; Daniela Gier Della Rocca; Belisa Alcantara Marinho; Sálvio Lima de Carvalho Neto; Maria de Fatima Rodrigues da Cunha; Luciana Prazeres Mazur; Regina F.P.M. Moreira; Adriano da Silva; Selene M.A. Guelli. U. de Souza; et al. (Chemical Engineering Journal, 2024)

Classic Presentation of Oral Paracoccidioidomycosis - Ana Cláudia Garcia Rosa; Daniela da Motta Rodrigues; Maribel Fernandez Fernandez; Eduardo Zambaldi da Cruz (Mycopathologia, 2024)

DNA lesions that block transcription induce the death of Trypanosoma cruzi via ATR activation, which is dependent on the presence of R-loops - Isabela Cecilia Mendes; Willian dos Reis Bertoldo; Adalberto Sales Miranda-Junior; Antônio Vinícius de Assis; Bruno Marçal Repolês; Wesley Roger Rodrigues Ferreira; Daniela Ferreira Chame; Daniela De Laet Souza; Raphael Souza Pavani; Andrea Mara Macedo; Glória Regina Franco; Esteban Serra; et al. (DNA Repair, 2024)

Alterations in neurotransmitters, steroid hormones, vitellogenin, and antioxidant system induced by di-n-butyl phthalate and di-isopentyl phthalate on catfish Rhamdia quelen - Izonete Cristina Guiloski; Taynah Vicari; Maiara Vicentini; Laís Fernanda Oya-Silva; Lucicleide Ângelo Silva Jungles Carvalho; Bruna Deda; Fellip Rodrigues Marcondes; Rafael Dias Simeoni; Gisele de Oliveira Guaita; Cristina Aparecida Jark Stern; Anderson Joel Martino-Andrade; Daniela Morais Leme; et al. (Environmental Science and Pollution Research, 2024)

CuO nanoparticles’ effect on the photosynthetic performance in seed tissues of Inga laurina (Fabaceae) - Daniela Espanguer Graciano; Montcharles Silva Pontes; Leandro Oliveira Araujo; Regiane Godoy Lima; Renato Grillo; Amilcar Machulek; Etenaldo Felipe Santiago; Samuel Leite Oliveira; Anderson Rodrigues Lima Caires (Environmental Science and Pollution Research, 2024)

Does host migration affect host-parasite interaction? Migrant birds harbor exclusive parasites but have similar roles in parasite-host networks - Daniela de Angeli Dutra; Raquel Andrade Rodrigues; Mauro Pichorim; Patrícia de Abreu Moreira; Érika Martins Braga (Oecologia, 2024)

Alkaloids (emetine and cephalin) production – affected by full sunlight stress in Carapichea ipecacuanha - Cristina Moll Hüther; Vitor Francisco Ferreira; Fernando de Carvalho da Silva; Wilson da Costa Santos; Junior Borella; Ramonn Diego Barros de Almeida; Daniela Marques Correia; Glauce Christian Alves Duarte; Ana Claudia Langaro; Julia Ramos de Oliveira; Jóice Azeredo Silva; Thelma de Barros Machado; et al. (Natural Product Research, 2024)

A comprehensive compilation of Iberian Medusozoan data: Diversity, ecology, and omics insights - Tomás Rodrigues; Daniela Almeida; Francisco A. Guardiola; Paulo A.V. Borges; Agostinho Antunes (Regional Studies in Marine Science, 2024)

The evaluation of skin sensitization potential of the UVCB substance diisopentyl phthalate by in silico and in vitro methods - Isisdoris Rodrigues de Souza; Martina Iulini; Valentina Galbiati; Ana Carolina Rodrigues; Daniela Fiori Gradia; Anderson J. M. Andrade; James W. Firman; Cynthia Pestana; Daniela Morais Leme; Emanuela Corsini (Archives of Toxicology, 2024)
Diisopentyl phthalate (DiPeP) is primarily used as a plasticizer or additive within the production of polyvinyl chloride (PVC), and has many additional industrial applications. Its metabolites were recently found in urinary samples of pregnant women; thus, this substance is of concern as relates to human exposure. Depending upon the nature of the alcohol used in its synthesis, DiPeP may exist either as a mixture consisting of several branched positional isomers, or as a single defined structure. This article investigates the skin sensitization potential and immunomodulatory effects of DiPeP CAS No. 84777-06-0, which is currently marketed and classified as a UVCB substance, by in silico and in vitro methods. Our findings showed an immunomodulatory effect for DiPeP in LPS-induced THP-1 activation assay (increased CD54 expression). In silico predictions using QSAR TOOLBOX 4.5, ToxTree, and VEGA did not identify DiPeP, in the form of a discrete compound, as a skin sensitizer. The keratinocyte activation (Key Event 2 (KE2) of the adverse outcome pathway (AOP) for skin sensitization) was evaluated by two different test methods (HaCaT assay and RHE assay), and results were discordant. While the HaCaT assay showed that DiPeP can activate keratinocytes (increased levels of IL-6, IL-8, IL-1α, and ILA gene expression), in the RHE assay, DiPeP slightly increased IL-6 release. Although inconclusive for KE2, the role of DiPeP in KE3 (dendritic cell activation) was demonstrated by the increased levels of CD54 and IL-8 and TNF-α in THP-1 cells (THP-1 activation assay). Altogether, findings were inconclusive regarding the skin sensitization potential of the UVCB DiPeP—disagreeing with the results of DiPeP in the form of discrete compound (skin sensitizer by the LLNA assay). Additional studies are needed to elucidate the differences between DiPeP isomer forms, and to better understand the applicability domains of non-animal methods in identifying skin sensitization hazards of UVCB substances.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Ecotoxicological strategies employing biochemical markers and organisms to monitor the efficacy of malathion photolysis treatment - Rafaela Imoski; Laís Jarenko da Cruz; Angela Maria Palacio-Cortés; Ana Marta Schafaschek; Eric Schwamberger; Pamella Regina Mariotti; Andre Luis Bichibichi Borges; Fernando Rodrigues-Silva; Liziê Daniela Tentler Prola; Mario Antônio Navarro da Silva; Adriane Martins de Freitas; Marcus Vinicius de Liz (Chemosphere, 2024)

Seasonality in Crotalus durissus venom - Lidia Jorge Tasima; Eduardo Oliveira Venâncio de Lima; Daniela Miki Hatakeyama; Jarbas Prado Vidueiros; Daniel Rodrigues Stuginski; Kathleen Fernandes Grego; Anita Mitico Tanaka-Azevedo (Toxicon, 2024)

ENSO effects on the relationship between aerosols and evapotranspiration in the south of the Amazon biome - Rafael Palácios; Daniela Castagna; Luzinete Barbosa; Adilson P. Souza; Breno Imbiriba; Cornélio A. Zolin; Danielle Nassarden; Leilane Duarte; Fernando G. Morais; Marco A. Franco; Glauber Cirino; Paulo Kuhn; et al. (Environmental Research, 2024)

Biopesticide spinosad: Unraveling ecotoxicological effects on zebrafish, Danio rerio - Inês Amaral; Sara C. Antunes; Daniela Rebelo; António Paulo Carvalho; Sara Rodrigues (Environmental Toxicology and Pharmacology, 2024)

Erythropoietin effects on cryopreserved/transplanted cat ovarian tissue: A comparison of two incubation methods - Isabella M.G. Silva; Aline Q. Rodrigues; Rayane B. Ribeiro; Beatriz A. Aguiar; Anne E.S.P. Marinho; Elisa A.M. Souza; Yasmin B. Ferreira; Victoria C.O. Azevedo; Daniela M. Oliveira; Sônia N. Báo; Jair T. Goulart; Carolina M. Lucci; et al. (Cryobiology, 2024)

Effects of organic and inorganic selenium supplementation on frozen-thawed ram semen at two cooling periods - Jéssica Ferreira Rodrigues; Lucas Dalle Laste Dacampo; Diogo Ferreira Bicca; Diogo Seibert Lüdtke; Daniela dos Santos Brum; Francielli Weber Santos Cibin (Veterinary Research Communications, 2024)

Combinatoriality and Compositionality in Communication, Skills, Tool Use, and Language - Nathalie Gontier; Stefan Hartmann; Michael Pleyer; Evelina Daniela Rodrigues (International Journal of Primatology, 2024)

Ultraviolet light C prototype device against Sporothrix brasiliensis as a potential physical method for surface disinfection - Anderson Luis Terçola; Vanice Rodrigues Poester; Lívia Silveira Munhoz; Daniela Fernandes Ramos; Anderson Favero Porte; Marcelo Moraes Galarça; Melissa Orzechowski Xavier (Brazilian Journal of Microbiology, 2024)

Recurrent community-acquired pneumococcal meningitis in adults with and without identified predisposing factors - Maria Cecilia Cergole-Novella; Elaine Monteiro Matsuda; Mariana Brena de Souza; Daniela Rodrigues Colpas; Andréia Moreira dos Santos Carmo; Vilma dos Santos Menezes Gaiotto Daros; Ivana Barros Campos (Brazilian Journal of Microbiology, 2024)

Alternative system for micropropagation of Prunus campanulata (Maxim.) - Daniela Sanson; Alexandre Techy de Almeida Garrett; Isy Cavalhães Rodrigues; Gabriel de Magalhães Miranda; Fabricio William de Ávila; Cristiane Alves Fogaça; Ezequiel Gasparin; Rogério Bobrowski; Fabiana Schmidt Bandeira Peres (In Vitro Cellular & Developmental Biology - Plant, 2024)

Evaluation of Mastadenovirus and Rotavirus Presence in Phyllostomid, Vespertilionid, and Molossid Bats Captured in Rio Grande do Sul, Southern Brazil - Alexandre Sita; Gabriela Espíndola Birlem; Deivid de Souza da Silva; Gabriela Mattos Possamai; Karla Petry; Paula Rodrigues de Almeida; Larissa Mallmann; Janaína Franciele Stein; Meriane Demoliner; Juliana Schons Gularte; Alana Witt Hansen; André Alberto Witt; et al. (Food and Environmental Virology, 2024)

The cost of genetic diagnosis of suspected hereditary pediatric cataracts with whole-exome sequencing from a middle-income country perspective: a mixed costing analysis - Luiza M. Neves; Márcia Pinto; Olivia A. Zin; Daniela P. Cunha; Bruna N. S. Agonigi; Fabiana L. Motta; Leonardo H. F. Gomes; Dafne D. G. Horovitz; Daltro C. Almeida; Jocieli Malacarne; Leticia Guida; Andressa Braga; et al. (Journal of Community Genetics, 2024)
Up to 25% of pediatric cataract cases are inherited. There is sparse information in the literature regarding the cost of whole-exome sequencing (WES) for suspected hereditary pediatric cataracts. Molecular diagnosis of suspected hereditary pediatric cataracts is important for comprehensive genetic counseling. We performed a partial economic evaluation with a mixed costing analysis, using reimbursement data and microcosting approach with a bottom-up technique to estimate the cost of using WES for genetic diagnosis of suspected hereditary pediatric cataracts from the perspective of the Brazilian governmental health care system. One hundred and ten participants from twenty-nine families in Rio de Janeiro (RJ) were included. Costs of consumables, staff and equipment were calculated. Two scenarios were created: (1) The reference scenario included patients from RJ with suspected hereditary pediatric cataracts plus two family members. (2) The alternative scenario considered other genetic diseases, resulting in 5,280 exams per month. Sensitivity analysis was also performed. In the reference scenario, the total cost per exam was 700.09 United States dollars (USD), and in the alternative scenario, the total cost was 559.23 USD. The cost of WES alone was 527.85 USD in the reference scenario and 386.98 USD in the alternative scenario. Sensitivity analysis revealed that the largest costs were associated with consumables in both scenarios. Economic evaluations can help inform policy decisions, especially in middle-income countries such as Brazil.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Mindful eating questionnaire: Validation and reliability in Brazilian adults with type 2 diabetes mellitus - Danielle Aparecida Caetano Rodrigues; Aline Marcadenti; Rachel H.V. Machado; Angela C. Bersch-Ferreira; Edilaine C.S. Gherardi-Donato; Driele Quinhoneiro; Jussara Carnevale de Almeida; Viviane Sahade Souza; Simone Raimondi de Souza; Fernanda Michielin Busnello; Daniela Corrêa Ferreira; Josefina Bressan; et al. (Appetite, 2024)

Body weight prediction in crossbred pigs from digital images using computer vision - Ana Caroline Rodrigues da Cunha; Robson Carlos Antunes; Weverton Gomes da Costa; Geovanne Ferreira Rebouças; Carla Daniela Suguimoto Leite; Adriana Santana do Carmo (Livestock Science, 2024)

Application Frequency and Colonization of the Rhizosphere of Strawberry (Fragaria x ananassa Duchesne) Plants by Azospirillum Brasilense - Altino Junior Mendes de Oliveira; Vytória Piscitelli Cavalcanti; Filipe Almendagna Rodrigues; Vera Lucia dos Santos; Aline Daniela Lopes Julio; Yulimar Castro Molina; Moacir Pasqual; Adalvan Daniel Martins; Léo Fufato; Joyce Dória (Journal of Plant Growth Regulation, 2024)

Comparing AGS Beers 2019, STOPP version 2, and EU(7)-PIM list in Portuguese older adults in primary health care - Daniela A. Rodrigues; Maria Teresa Herdeiro; Ramona Mateos-Campos; Adolfo Figueiras; Fátima Roque (European Journal of Clinical Pharmacology, 2024)
Purpose This study aims to identify PIM prevalence in older adults according to the 2019 Beers criteria, Screening Tool of Older Person’s Prescriptions version 2 (STOPP v2) criteria, and the Portuguese EU(7)-PIM list and also to analyze the concordance between these criteria. Methods A retrospective study was conducted among 1200 Portuguese older adults (≥ 65 years old), users of primary health care. Demographic, clinical, and pharmacological data were collected concerning the period between April 2021 and August 2022. A comparative analysis was performed between the three PIM identification criteria, and the concordance was determined according to the Lin concordance correlation coefficient. Results The mean age was 76.3 (SD 7.7) years old and 57.6% of the older adults were females. Our findings indicate varying prevalence rates among these criteria with 63.8% (95% CI 61.0–66.6%), 66.8% (95% CI 64.1–69.5%), and 50.1% (95% CI 47.2–53.0%) of the older adults take at least one PIM according to the EU(7)-PIM list, Beers 2019, and STOPP v2 criteria, respectively. The highest prevalence observed was for proton pump inhibitors according to EU(7)-PIM list (30.1%, 95% CI 27.6–32.9) and Beers criteria (30.1%, 95% CI 27.6–32.9) and alprazolam according to STOPP v2 criteria (10.1%, 95% CI 8.4–11.9%). A poor concordance between criteria was observed (< 0.834). The highest concordance coefficient was found between the EU(7)-PIM list and the Beers criteria (0.833), and the lowest between the EU(7)-PIM list and STOPP criteria (0.735). Conclusion This study reveals varying prevalence rates of PIM in older adults, as assessed by different criteria, and highlights the need for targeted interventions and improved prescribing practices. In the future, studies should focus on the occurrence of negative outcomes in older adults associated with PIM consumption.

Immunomodulatory effect of Lacticaseibacillus casei CB054 supplementation in calves vaccinated against infectious bovine rhinotracheitis - Carolina Litchina Brasil; Vitória Sequeira Gonçalves; Francisco Denis Souza Santos; Paulo Ricardo Centeno Rodrigues; Fábio Pereira Leivas Leite; Daniela Isabel Brayer Pereira (Veterinary Immunology and Immunopathology, 2024)

Soil Antibiotics: How Long Will This Matrix be Neglected? - Livia da Silva Freitas; Rodolfo Moreira Baptista; Flavio Manoel Rodrigues da Silva Júnior; Daniela Fernandes Ramos (Water, Air, & Soil Pollution, 2024)

Protective Association of APOC1/rs4420638 with Risk of Obesity: A case-control Study in Portuguese Children - Licínio Manco; David Albuquerque; Daniela Rodrigues; Aristides M. Machado-Rodrigues; Cristina Padez (Biochemical Genetics, 2024)
The association of the rs4420638 polymorphism, near the APOC1 gene, was examined with the risk of obesity among Portuguese children. A sample of 446 Portuguese individuals (231 boys and 215 girls) of European descent, aged 3.2 to 13.7 years old (mean age: 7.98 years), were selected to conduct a case-control study. Body mass index (BMI), BMI Z-scores, and waist circumference were calculated. Genotyping was performed by real time PCR using a pre-designed TaqMan probe. Logistic regression and the nonparametric Mann-Whitney test were used to test the associations. The association results revealed a significant protective effect from the minor G-allele of SNP rs4420638 against obesity, with an odds ratio (OR) of 0.619 (95% CI 0.421–0.913; p = 0.0155) in the additive model, and OR of 0.587 (95% CI 0.383-0.9; p = 0.0145) in the dominant model. Moreover, comparing genotype groups (AA vs. AG + GG), significantly lower values ( p APOE / APOC1 candidate-region association with the risk of obesity. This was the first study to describe the protective association of the rs4420638 minor G-allele against obesity in childhood exclusively.

Prediction of acute fish toxicity (AFT) and fish embryo toxicity (FET) tests by cytotoxicity assays using liver and embryo zebrafish cell lines (ZFL and ZEM2S) - Irisdoris Rodrigues de Souza; Júlia Beatriz Vaz de Oliveira; Tainá Wilke Sivek; Natália de Albuquerque Vita; Andrezza Di Pietro Micali Canavez; Desiree Cigaran Schuck; Marta Margarete Cestari; Márcio Lorencini; Daniela Morais Leme (Chemosphere, 2024)

Chromatic discrimination in fixed saturation levels from tufted capuchin monkeys with different color vision genotypes - Luiza Karina Gonçalves Meireles; Leticia Miquilini; Felipe André Costa Brito; Anderson Raiol Rodrigues; Leonardo Dutra Henriques; Einat Hauzman; Daniela Maria Oliveira Bonci; Marcelo Fernandes Costa; Olavo de Faria Galvão; Dora Fix Ventura; Paulo Roney Kilpp Goulart; Givago Silva Souza (Journal of Comparative Physiology A, 2024)

Professor Luiz R. Travassos and the study of surface structures of fungal pathogens - Marcio L. Rodrigues; Daniela S. Alviano; Lucimar F. Kneipp; Celuta S. Alviano; Eliana Barreto-Bergter; Leonardo Nimrichter (Brazilian Journal of Microbiology, 2023)

Evidence of genotoxicity, neurotoxicity, and antioxidant imbalance in silver catfish Rhamdia quelen after subchronic exposure to diisopentyl phthalate - Laís Fernanda Oya-Silva; Izonete Cristina Guiloski; Taynah Vicari; Bruna Deda; Fellip Rodrigues Marcondes; Rafael Dias Simeoni; Maiara Carolina Perussolo; Anderson Joel Martino-Andrade; Daniela Morais Leme; Helena Cristina Silva de Assis; Marta Margarete Cestari (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Effects of chemotherapeutic drugs on the antioxidant capacity of human erythroleukemia cells with MDR phenotype - Maiara Bernardes Marques; Filipe Reis Teodoro Andrade; Estela Fernandes e Silva; Bruno Rodrigues Oliveira; Daniela Volcan Almeida; Ana Paula de Souza Votto; Luis Fernando Marins (Molecular and Cellular Biochemistry, 2023)

Cohesion depends on kinship but no permanent leadership in larval societies of a Neotropical butterfly - Daniela Rodrigues; Felipe Lee Pinheiro Machado (The Science of Nature, 2023)

Larvicidal potential of extracts and isolated compounds from Piper cubeba fruits against Aedes aegypti (Diptera: Culicidae) larvae - Ana Carolina Gomes; Alexandre Borges; Daniela Garcia Zoca; Marcio Luís Andrade e Silva; Aline Rafaela da Silva Rodrigues Machado; Alex Martins Machado; Mario F. C. Santos; Rosangela da Silva de Laurentiz (Natural Product Research, 2023)

Synthetic silico-metallic particles-SSMMP-Ni and SSMMP-Ni-IL: CO2 capture and utilization - Daniela Rodrigues; Julia Wolf; Barbara Polesso; Pierre Micoud; Christophe Le Roux; Franciele Bernard; François Martin; Sandra Einloft (Fuel, 2023)

An integrated in silico-in vitro investigation to assess the skin sensitization potential of 4-Octylphenol - Isisdoris Rodrigues de Souza; Martina Iulini; Valentina Galbiati; Enzo Zini Moreira Silva; Tainá Wilke Sivek; Ana Carolina Rodrigues; Daniela Fiori Gradia; Cynthia Bomfim Pestana; Daniela Morais Leme; Emanuela Corsini (Toxicology, 2023)

Genomic evidences of gulls as reservoirs of critical priority CTX-M-producing Escherichia coli in Corcovado Gulf, Patagonia - Danny Fuentes-Castillo; Daniela Castro-Tardón; Fernanda Esposito; Ingrith Neves; Larissa Rodrigues; Herrison Fontana; Bruna Fuga; José L. Catão-Dias; Nilton Lincopan (Science of The Total Environment, 2023)

Intraspecific variation in ultrastructure and secretion of the resin canals in Anacardium humile (Anacardiaceae) - Shelly Favorito de Carvalho; Elton Luiz Scudeler; Daniela Carvalho dos Santos; Silvia Rodrigues Machado (Protoplasma, 2023)

Peroxisomes : novel findings and future directions - Ana G. Pedrosa; Katharina Reglinski; Celien Lismont; Suzan Kors; Joseph Costello; Tony A. Rodrigues; Mariana Marques; Nicole Linka; Catherine Argyriou; Isabelle Weinhofer; Sai Kocherlakota; Victoria Riccio; et al. (Histochemistry and Cell Biology, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Modeling the resilience of urban mobility when exposed to the COVID-19 pandemic: A qualitative system dynamics approach - Daniela Vanessa Rodriguez Lara; Paul Pfaffenbichler; Antônio Nélson Rodrigues da Silva (Sustainable Cities and Society, 2023)

Multiplex PCR to Streptococcus pneumoniae serotype identification directly in cerebrospinal fluid samples - Mariana Brena de Souza; Eneas de Carvalho; Maria Cecília Cergole-Novella; Delma Aparecida Molinari; Daniela Rodrigues Colpas; Andréia Moreira dos Santos Carmo; Vilma dos Santos Menezes Gaiotto Daros; Ivana Barros de Campos (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Antibacterial activity and physicochemical properties of a sealer containing copaiba oil - Lara Rodrigues Schneider; Andressa da Silva Barboza; Juliana Silva Ribeiro de Andrade; Daniela Coelho dos Santos; Carlos Enrique Cuevas-Suárez; Evandro Piva; Angela Diniz Campos; Rafael Guerra Lund (Biofouling, 2023)

Morphophysiological responses of comfrey ( Symphytum officinale ) to water deficit - Larissa Quirino da Silva; Cristina Moll Hüther; Natália Fernandes Rodrigues; Julia Ramos de Oliveira; Daniela Marques Correia; Bruno Garcia Ferreira; Vitor Francisco Ferreira; Mariana de Oliveira Pereira; Bruna de Carvalho Assunção; Gabriela Martins Corrêa; Filipe Rodrigues Valeriano; Leticia Ponticel Nobrega; et al. (Plant Biosystems, 2023)

Lightcurve analysis of near-Earth objects from the IMPACTON project: Evidence of binary systems and cohesion strength - Filipe Monteiro; Daniela Lazzaro; Eduardo Rondón; Plícida Arcoverde; Marçal Evangelista-Santana; Jonatan Michimani; Weslley Pereira; Wesley Mesquita; Hissa Medeiros; Tatiane Corrêa; José Silva-Cabrera; Teresinha Rodrigues (Icarus, 2023)

Occurrence and distribution of per-and polyfluoroalkyl substances (PFAS) in surface and groundwaters in an urbanized and agricultural area, Southern Brazil - Paulo Henrique Prado Stefano; Ari Roisenberg; Raphael D’Anna Acayaba; Aline Pereira Roque; Daniela Rodrigues Bandoria; Aluisio Soares; Cassiana Carolina Montagner (Environmental Science and Pollution Research, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Anti-Aspergillus fumigatus IgG in patients with bronchiectasis and its relationship with clinical outcome - Mariana Rodrigues Trápaga; Vanice Rodrigues Poester; Karine Ortiz Sanchotene; Aryse Martins Melo; Jéssica Louise Benelli; Rossana Patricia Basso; Gabriel Baracy Klafke; Daniela Fernandes Ramos; Cristina Veríssimo; Raquel Sabino; David A. Stevens; Melissa Orzechowski Xavier (Archives of Microbiology, 2022)

Enhancement of chlorhexidine activity against planktonic and biofilm forms of oral streptococci by two Croton spp. essential oils from the Caatinga biome - Brendda Miranda Vasconcelos; Antônio Mateus Gomes Pereira; Paulo Adenes Teixeira Coelho; Rafaela Mesquita Bastos Cavalcante; Daniela Santos Carneiro-Torres; Paulo Nogueira Bandeira; Felipe Ferreira da Silva; Tigressa Helena Soares Rodrigues; Geovany Amorim Gomes; Victor Alves Carneiro (Biofouling, 2022)

Pediatric cerebral sinus venous thrombosis: clinical characterization of a Portuguese cohort - Sofia Grenho Rodrigues; Daniela Vieira; Francisco Bernardo; Joana Coelho; Joana Afonso Ribeiro; Filipe Palavra; Conceição Robalo; António Levy; Sofia Quintas (Acta Neurologica Belgica, 2022)

Metabolic Profile of the Soil Microbial Community Exposed to Arsenite and Arsenate: a 1-Year Experiment - Rodrigo de Lima Brum; Lisiane Martins Volcão; Livia da Silva Freitas; Jessica El Koury Santos; Mariana Vieira Coronas; Juliane Ventura-Lima; Daiane Dias; Bruno Meira Soares; Erico Kunde Corrêa; Ng Haig They; Daniela Fernandes Ramos; Flavio Manoel Rodrigues da Silva Júnior (Water, Air, & Soil Pollution, 2022)

Tuberculosis/COVID-19 co-infection detected in a single sputum sample using a rapid molecular test - Akemi Oshiro Guirelli; Thayná Rosa Bispo; Daniela Rodrigues Colpas; Ivana Barros de Campos; Erica Chimara; Maria Cecília Cergole-Novella; Itatiana Ferreira Rodart; Valéria dos Santos Candido; Paula Jimena Segura-Ramírez; Vilma dos Santos Menezes Gaiotto Daros; Andreia Moreira dos Santos Carmo (Brazilian Journal of Microbiology, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Which birds are Brazilians seeing on urban and non-urban feeders? An analysis based on a collective online birding - Eduardo Roberto Alexandrino; Thaís Abreu Camboim; Flávia Guimarães Chaves; Alex Augusto Abreu Bovo; Marco Aurélio Galvão da Silva; Daniela Alves Maia da Silva; Margi Moss; Tatiana Pongiluppi Souza; Clarissa de Oliveira Santos; Caio Bezerra de Mattos Brito; Maristela Camolesi Alcantara; Karlla V. C. Barbosa; et al. (Ornithology Research, 2022)

Removal of Methyl Violet Dye by Adsorption Process on Hydrogen Titanate Nanotubes: Experimental-Theoretical Study - Daniela Kelly dos Santos; Renata Treméa; Eudes Lorençon; Patrick Rodrigues Batista; Lucila Adriani de Almeida Coral; Fatima de Jesus Bassetti (Water, Air, & Soil Pollution, 2022)

Development of 3D cultures of zebrafish liver and embryo cell lines: a comparison of different spheroid formation methods - Irisdoris Rodrigues de Souza; Andrezza Di Pietro Micali Canavez; Desiree Cigaran Schuck; Viviana Stephanie Costa Gagosian; Isisdoris Rodrigues de Souza; Taynah Vicari; Edvaldo da Silva Trindade; Marta Margarete Cestari; Marcio Lorencini; Daniela Morais Leme (Ecotoxicology, 2021)

Variability in Seaweed Chemical Defense and Growth Under Common Garden Conditions - Daniela Bueno Sudatti; Aline Santos Oliveira; Bernardo Antonio Perez da Gama; Mutue Toyota Fujii; Silvana Vianna Rodrigues; Renato Crespo Pereira (Frontiers in Marine Science, 2021)

Jundiá Fish Skin ( Rhamdia quelen ): An Unexplored By-product with Great Potential to Be Used as a Novel Source of Collagen - Camila Giacomelli Da Silva; Angela Souza Rodrigues; Daniela Pedrolo Weber Toniasso; Fernando Dal Pont Morisso; Paulo Cezar Bastianello Campagnol; Renius de Oliveira Mello; Rosa Cristina Prestes Dornelles; Ernesto Hashime Kubota (Journal of Aquatic Food Product Technology, 2021)

Swine polioencephalomyelitis in Brazil: identification of Teschovirus A, Sapelovirus A, and Enterovirus G in a farm from Southern Brazil - Márcia Elisa Hammerschmitt; Paula Rodrigues de Almeida; Bianca Santana de Cecco; Marina Paula Lorenzett; Claiton Ismael Schwertz; Raquel Aparecida Sales da Cruz; Rafaela Albuquerque Caprioli; Daniela Teresa Schuh; Meriane Demoliner; Ana Karolina Antunes Eisen; Fernando Rosado Spilki; Saulo Petinatti Pavarini; et al. (Brazilian Journal of Microbiology, 2021)

Chemical, physical, and biological attributes in soils affected by deposition of iron ore tailings from the Fundão Dam failure - Aline Oliveira Silva; Amanda Azarias Guimarães; Bruna Daniela Ortiz Lopez; Carin Sgobi Zanchi; Cesar Florentino Puma Vega; Éder Rodrigues Batista; Fatima Maria de Souza Moreira; Flávia Romam da Costa Souza; Flávio Araújo Pinto; Jessé Valentim dos Santos; Joana Junqueira Carneiro; José Oswaldo Siqueira; et al. (Environmental Monitoring and Assessment, 2021)

New insights into the mechanisms underlying 5-fluorouracil-induced intestinal toxicity based on transcriptomic and metabolomic responses in human intestinal organoids - Daniela Rodrigues; Terezinha de Souza; Luke Coyle; Matteo Di Piazza; Bram Herpers; Sofia Ferreira; Mian Zhang; Johanna Vappiani; Daniel C. Sévin; Attila Gabor; Anthony Lynch; Seung-Wook Chung; et al. (Archives of Toxicology, 2021)
5-Fluorouracil (5-FU) is a widely used chemotherapeutical that induces acute toxicity in the small and large intestine of patients. Symptoms can be severe and lead to the interruption of cancer treatments. However, there is limited understanding of the molecular mechanisms underlying 5-FU-induced intestinal toxicity. In this study, well-established 3D organoid models of human colon and small intestine (SI) were used to characterize 5-FU transcriptomic and metabolomic responses. Clinically relevant 5-FU concentrations for in vitro testing in organoids were established using physiologically based pharmacokinetic simulation of dosing regimens recommended for cancer patients, resulting in exposures to 10, 100 and 1000 µM. After treatment, different measurements were performed: cell viability and apoptosis; image analysis of cell morphological changes; RNA sequencing; and metabolome analysis of supernatant from organoids cultures. Based on analysis of the differentially expressed genes, the most prominent molecular pathways affected by 5-FU included cell cycle, p53 signalling, mitochondrial ATP synthesis and apoptosis. Short time-series expression miner demonstrated tissue-specific mechanisms affected by 5-FU, namely biosynthesis and transport of small molecules, and mRNA translation for colon; cell signalling mediated by Rho GTPases and fork-head box transcription factors for SI. Metabolomic analysis showed that in addition to the effects on TCA cycle and oxidative stress in both organoids, tissue-specific metabolic alterations were also induced by 5-FU. Multi-omics integration identified transcription factor E2F1, a regulator of cell cycle and apoptosis, as the best key node across all samples. These results provide new insights into 5-FU toxicity mechanisms and underline the relevance of human organoid models in the safety assessment in drug development.

Correction to: Association of ionophores, yeast, and bacterial probiotics alters the abundance of ruminal microbial species of pasture intensively finished beef cattle - Mircéia Angele Mombach; Luciano da Silva Cabral; Leni Rodrigues Lima; Daniela Cristina Ferreira; Bruno Carneiro e Pedreira; Dalton Henrique Pereira (Tropical Animal Health and Production, 2021)

Bioassays for the evaluation of reclaimed opencast coal mining areas - Laiz Coutelle Honscha; Audrey Senandes Campos; Ronan Adler Tavella; Paula Florencio Ramires; Lisiane Martins Volcão; Priscila Cristina Bartolomeu Halicki; Tatiani Maria Pech; Eduardo Bernardi; Daniela Fernandes Ramos; Júlia Carina Niemeyer; Paulo Roberto Martins Baisch; Ana Luíza Muccillo Baisch; et al. (Environmental Science and Pollution Research, 2021)

Factors influencing endothelial cell density of corneas for transplantation - Thatiane Lima Sampaio; Isabela Pereira Rodrigues; Micheline Borges Lucas Cresta; Anna Cláudia de Oliveira Queiroz; Thayssa Neiva da Fonseca Victer; Daniela Ferreira Salomão Pontes; Wildo Navegantes de Araújo; Sônia Nair Báo; Maria Regina Catai Chalita (Cell and Tissue Banking, 2021)

Human-modified landscapes narrow the isotopic niche of neotropical birds - Ana Beatriz Navarro; Marcelo Magioli; Juliano André Bogoni; Marcelo Zacharias Moreira; Luís Fábio Silveira; Eduardo Roberto Alexandrino; Daniela Tomasio Apolinario da Luz; Marco Aurelio Pizo; Wesley Rodrigues Silva; Vanessa Cristina de Oliveira; Reginaldo José Donatelli; Alexander V. Christianini; et al. (Oecologia, 2021)

Treatment of a clinical analysis laboratory wastewater from a hospital by photo-Fenton process at four radiation settings and toxicity response - Roberson Davis Sá; Adriana Patricia Rodríguez-Pérez; Fernando Rodrigues-Silva; Vinicius de Carvalho Soares de Paula; Liziê Daniela Tentler Prola; Adriane Martins de Freitas; Karina Querne de Carvalho; Marcus Vinicius de Liz (Environmental Science and Pollution Research, 2021)

Association of ionophores, yeast, and bacterial probiotics alters the abundance of ruminal microbial species of pasture intensively finished beef cattle - Mircéia Angele Mombach; Luciano da Silva Cabral; Leni Rodrigues Lima; Daniela Cristina Ferreira; Bruno Carneiro e Pedreira; Dalton Henrique Pereira (Tropical Animal Health and Production, 2021)

Performance of broiler chicken submitted to a quantitative feed restriction program - Tiago Bordin; Fernando Pilotto; Daniela Pesenatto; Bruno Sebastião de Mendonça; Luciane Daroit; Laura Beatriz Rodrigues; Ezequiel Davi dos Santos; Elci Lotar Dickel (Tropical Animal Health and Production, 2021)

Influence of microcurrent on the modulation of remodelling genes in a wound healing assay - Daniela Fernanda Dezotti Silva; Lucas de Oliveira Fujii; Gabriela Bortolança Chiarotto; Camila Andrea de Oliveira; Thiago Antônio Moretti de Andrade; Alexandre Leite Rodrigues de Oliveira; Marcelo Augusto Marretto Esquisatto; Fernanda Aparecida Sampaio Mendonça; Gláucia Maria Tech dos Santos; Andrea Aparecida de Aro (Molecular Biology Reports, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Drought-induced stress in leaves of Coix lacryma-jobi L. under exogenous application of proline and GABA amino acids - Rafael Agostinho Ferreira; Junior Borella; Cristina Moll Hüther; Ana Carolina Barbosa do Canto; Nathan Pereira da Costa Correa; Daniela Marques Correia; Rubiana Pereira Borges; Camila Ferreira de Pinho; Thelma de Barros Machado; Carlos Rodrigues Pereira (Brazilian Journal of Botany, 2020)

Antifungal compounds with anticancer potential from Trichoderma sp. P8BDA1F1, an endophytic fungus from Begonia venosa - Diana F. Grigoletto; Daniela B. B. Trivella; André G. Tempone; André Rodrigues; Ana Maria L. Correia; Simone P. Lira (Brazilian Journal of Microbiology, 2020)

Assessment of susceptibility to landslides through geographic information systems and the logistic regression model - Roberta Plangg Riegel; Darlan Daniel Alves; Bruna Caroline Schmidt; Guilherme Garcia de Oliveira; Claus Haetinger; Daniela Montanari Migliavacca Osório; Marco Antônio Siqueira Rodrigues; Daniela Muller de Quevedo (Natural Hazards, 2020)

Danaus butterflies of the Americas do not perform leaf-scratching - Bruna de Cássia Menezes Ramos; José Roberto Trigo; Daniela Rodrigues (Arthropod-Plant Interactions, 2020)

Toxicity of Biocide Formulations in the Soil to the Gut Community in Balloniscus selowii Brandt, 1983 (Crustacea: Isopoda: Oniscidea) - Lisiane Martins Volcão; Letícia Schmidt Fraga; Rodrigo de Lima Brum; Renata Rodrigues de Moura; Eduardo Bernardi; Daniela Fernandes Ramos; Flávio Manoel Rodrigues da Silva Júnior (Water, Air, & Soil Pollution, 2020)

Evolutionary and Functional Implications of Incisor Enamel Microstructure Diversity in Notoungulata (Placentalia, Mammalia) - Andréa Filippo; Daniela C. Kalthoff; Guillaume Billet; Helder Gomes Rodrigues (Journal of Mammalian Evolution, 2020)

Correction to: In vitro mechanistic studies on α-amanitin and its putative antidotes - Daniela Ferreira Rodrigues; Ricardo Pires das Neves; Alexandra T. P. Carvalho; Maria Lourdes Bastos; Vera M. Costa; Félix Carvalho (Archives of Toxicology, 2020)

In vitro mechanistic studies on α-amanitin and its putative antidotes - Daniela Ferreira Rodrigues; Ricardo Pires das Neves; Alexandra T. P. Carvalho; Maria Lourdes Bastos; Vera M. Costa; Félix Carvalho (Archives of Toxicology, 2020)

Identification of genes from the general phenylpropanoid and monolignol-specific metabolism in two sugarcane lignin-contrasting genotypes - Douglas Jardim-Messeder; Tatiane da Franca Silva; Jose Pedro Fonseca; José Nicomedes Junior; Lucia Barzilai; Thais Felix-Cordeiro; Joyce Carvalho Pereira; Clara Rodrigues-Ferreira; Isabela Bastos; Tereza Cristina da Silva; Vinicius de Abreu Waldow; Daniela Cassol; et al. (Molecular Genetics and Genomics, 2020)

A risk-based multi-level stress test methodology: application to six critical non-nuclear infrastructures in Europe - Sotirios A. Argyroudis; Stavroula Fotopoulou; Stella Karafagka; Kyriazis Pitilakis; Jacopo Selva; Ernesto Salzano; Anna Basco; Helen Crowley; Daniela Rodrigues; José P. Matos; Anton J. Schleiss; Wim Courage; et al. (Natural Hazards, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Expression of MicroRNAs miR-145, miR-181c, miR-199a and miR-1183 in the Blood and Hippocampus of Patients with Mesial Temporal Lobe Epilepsy - Luana Grupioni Lourenço Antônio; Priscila Freitas-Lima; Gabriela Pereira-da-Silva; João Alberto Assirati; Caio Marconato Matias; Mucio Luiz Assis Cirino; Luis Fernando Tirapelli; Tonicarlo Rodrigues Velasco; Americo Ceiki Sakamoto; Carlos Gilberto Carlotti; Daniela Pretti da Cunha Tirapelli (Journal of Molecular Neuroscience, 2019)

Toxicological evaluation of nail polish waste discarded in the environment - Israel Felzenszwalb; Andreia da Silva Fernandes; Lara Barroso Brito; Gisele Augusto Rodrigues Oliveira; Paula Aquino Soeiro Silva; Maria Elena Arcanjo; Monica Regina da Costa Marques; Taynah Vicari; Daniela Morais Leme; Marta Margarete Cestari; Elisa Raquel Anastacio Ferraz (Environmental Science and Pollution Research, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

An effective antidotal combination of polymyxin B and methylprednisolone for α-amanitin intoxication - Juliana Garcia; Vera Marisa Costa; Antonio Bovolini; José Alberto Duarte; Daniela Ferreira Rodrigues; Maria de Lourdes Bastos; Félix Carvalho (Archives of Toxicology, 2019)

Strength training and aerobic exercise alter mitochondrial parameters in brown adipose tissue and equally reduce body adiposity in aged rats - Anand Thirupathi; Bruno Luiz da Silva Pieri; João Annibal Milano Peixoto Queiroz; Matheus Scarpatto Rodrigues; Gustavo de Bem Silveira; Daniela Roxo de Souza; Thais Fernandes Luciano; Paulo Cesar Lock Silveira; Claudio Teodoro De Souza (Journal of Physiology and Biochemistry, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Medusozoa in Portugal: impact on the ecosystems and development of DNA-based tools for the early forecasting of mass occurrences - Tomás Rodrigues; Ana Matos; Dany Domínguez-Pérez; Joana Falcão; Sónia Marques; Sérgio Leandro; Daniela Almeida; Agostinho Antunes (Frontiers in Marine Science, 2019)

Medusozoa in Portugal: impact on the ecosystems and development of DNA-based tools for the early forecasting of mass occurrences - Tomás Rodrigues; Ana Matos; Dany Domínguez-Pérez; Joana Falcão; Sónia Marques; Sérgio Leandro; Daniela Almeida; Agostinho Antunes (Frontiers in Marine Science, 2019)

Perinatal Asphyxia and Brain Development: Mitochondrial Damage Without Anatomical or Cellular Losses - Jean Pierre Mendes Lima; Danielle Rayêe; Thaia Silva-Rodrigues; Paula Ribeiro Paes Pereira; Ana Paula Miranda Mendonca; Clara Rodrigues-Ferreira; Diego Szczupak; Anna Fonseca; Marcus F. Oliveira; Flavia Regina Souza Lima; Roberto Lent; Antonio Galina; et al. (Molecular Neurobiology, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

ATLANTIC BIRDS : a data set of bird species from the Brazilian Atlantic Forest - Érica Hasui; Jean Paul Metzger; Rafael G. Pimentel; Luís Fábio Silveira; Alex A. d. A. Bovo; Alexandre C. Martensen; Alexandre Uezu; André L. Regolin; Arthur Â. Bispo de Oliveira; Cassiano A. F. R. Gatto; Charles Duca; Christian B. Andretti; et al. (Ecology, 2018)
South America holds 30% of the world's avifauna, with the Atlantic Forest representing one of the richest regions of the Neotropics. Here we have compiled a data set on Brazilian Atlantic Forest bird occurrence (150,423) and abundance samples ( N = 832 bird species; 33,119 bird individuals) using multiple methods, including qualitative surveys, mist nets, point counts, and line transects). We used four main sources of data: museum collections, on‐line databases, literature sources, and unpublished reports. The data set comprises 4,122 localities and data from 1815 to 2017. Most studies were conducted in the Florestas de Interior (1,510 localities) and Serra do Mar (1,280 localities) biogeographic sub‐regions. Considering the three main quantitative methods (mist net, point count, and line transect), we compiled abundance data for 745 species in 576 communities. In the data set, the most frequent species were Basileuterus culicivorus , Cyclaris gujanensis , and Conophaga lineata . There were 71 singletons, such as Lipaugus conditus and Calyptura cristata . We suggest that this small number of records reinforces the critical situation of these taxa in the Atlantic Forest. The information provided in this data set can be used for macroecological studies and to foster conservation strategies in this biodiversity hotspot. No copyright restrictions are associated with the data set. Please cite this Data Paper if data are used in publications and teaching events.

Earthquake loss assessment of precast RC industrial structures in Tuscany (Italy) - Daniela Rodrigues; Helen Crowley; Vitor Silva (Bulletin of Earthquake Engineering, 2018)

Role of Dynein Axonemal Heavy Chain 6 Gene Expression as a Possible Biomarker for Huntington’s Disease: a Translational Study - Lorena B. Areal; Lorraine P. Pereira; Fabiola M. Ribeiro; Isabella G. Olmo; Marcelo R. Muniz; Maria do Carmo Rodrigues; Patrik F. Costa; Cristina Martins-Silva; Stephen S. G. Ferguson; Daniela A. M. Guimarães; Rita G. W. Pires (Journal of Molecular Neuroscience, 2017)

Larval aggregation in a Neotropical butterfly: risky behaviors, per capita risk, and larval responses in Ascia monuste orseis - Alessandra F. K. Santana; Daniela Rodrigues; Fernando S. Zucoloto (Behavioral Ecology and Sociobiology, 2017)

Caffeine Reverts Memory But Not Mood Impairment in a Depression-Prone Mouse Strain with Up-Regulated Adenosine A2A Receptor in Hippocampal Glutamate Synapses - Nuno J. Machado; Ana Patrícia Simões; Henrique B. Silva; Ana Paula Ardais; Manuella P. Kaster; Pedro Garção; Diana I. Rodrigues; Daniela Pochmann; Ana Isabel Santos; Inês M. Araújo; Lisiane O. Porciúncula; Ângelo R. Tomé; et al. (Molecular Neurobiology, 2017)

Evaluating genotoxic risks in Brazilian public health agents occupationally exposed to pesticides: a multi-biomarker approach - Fernanda Craveiro Franco; Alessandro Arruda Alves; Fernanda Ribeiro Godoy; Juliana Boaventura Avelar; Douglas Dantas Rodrigues; Thays Millena Alves Pedroso; Aparecido Divino da Cruz; Fausto Nomura; Daniela de Melo e Silva (Environmental Science and Pollution Research, 2016)

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

Sulfasalazine intensifies temozolomide cytotoxicity in human glioblastoma cells - Raffaela Silvestre Ignarro; Gustavo Facchini; André Schwambach Vieira; Daniela Rodrigues De Melo; Iscia Lopes-Cendes; Roger Frigério Castilho; Fabio Rogerio (Molecular and Cellular Biochemistry, 2016)

Thioridazine inhibits gene expression control of the cell wall signaling pathway (CWI) in the human pathogenic fungus Paracoccidioides brasiliensis - Daniela Leite Jabes; Ana Claudia de Freitas Oliveira; Valquíria Campos Alencar; Fabiano Bezerra Menegidio; Débora Liliane Souza Reno; Daiene Souza Santos; David Aciole Barbosa; Renata Ozelami Vilas Boas; Rodrigo Luiz de Oliveira Rodrigues Cunha; Tiago Rodrigues; Regina Costa de Oliveira; Luiz R. Nunes (Molecular Genetics and Genomics, 2016)

Oviposition in Heliconius erato (Lepidoptera, Nymphalidae): how Essential Is Drumming Behavior for Host-Plant Selection? - Sabrina C. Thiele; Daniela Rodrigues; Gilson R.P. Moreira (Journal of Insect Behavior, 2016)

Canine fetal echocardiography: correlations for the analysis of cardiac dimensions - Amália Turner Giannico; Elaine Mayumi Ueno Gil; Daniela Aparecida Ayres Garcia; Marlos Gonçalves Sousa; Tilde Rodrigues Froes (Veterinary Research Communications, 2016)

Erratum to: Ferulic acid chronic treatment exerts antidepressant-like effect: role of antioxidant defense system - Juliana Lenzi; Andre Felipe Rodrigues; Adriana de Sousa Rós; Amanda Blanski de Castro; Daniela Delwing de Lima; Débora Delwing Dal Magro; Ana Lúcia Bertarello Zeni (Metabolic Brain Disease, 2015)

Ferulic acid chronic treatment exerts antidepressant-like effect: role of antioxidant defense system - Juliana Lenzi; Andre Felipe Rodrigues; Adriana de Sousa Rós; Bianca Blanski de Castro; Daniela Delwing de Lima; Débora Delwing Dal Magro; Ana Lúcia Bertarello Zeni (Metabolic Brain Disease, 2015)

Prevalence of Mycobacterium avium subsp. paratuberculosis and Escherichia coli in blood samples from patients with inflammatory bowel disease - Nair Nazareth; Fernando Magro; Elisabete Machado; Teresa Gonçalves Ribeiro; António Martinho; Pedro Rodrigues; Rita Alves; Gonçalo Nuno Macedo; Daniela Gracio; Rosa Coelho; Candida Abreu; Rui Appelberg; et al. (Medical Microbiology and Immunology, 2015)

Human adenovirus spread, rainfalls, and the occurrence of gastroenteritis cases in a Brazilian basin - Manoela Tressoldi Rodrigues; Andréia Henzel; Rodrigo Staggemeier; Daniela Muller de Quevedo; Caroline Rigotto; Larissa Heinzelmann; Carlos Augusto do Nascimento; Fernando Rosado Spilki (Environmental Monitoring and Assessment, 2015)

Sabotaging Behavior and Decision-Making in Larvae of the Queen Butterfly Danaus gilippus - Pedro P. S. Ferreira; Daniela Rodrigues (Journal of Insect Behavior, 2015)

Southern Monarchs do not Develop Learned Preferences for Flowers With Pyrrolizidine Alkaloids - Marina Vasconcelos de Oliveira; José Roberto Trigo; Daniela Rodrigues (Journal of Chemical Ecology, 2015)

A Kinetic Characterization of (Na+, K+)-ATPase Activity in the Gills of the Pelagic Seabob Shrimp Xiphopenaeus kroyeri (Decapoda, Penaeidae) - Francisco Assis Leone; Malson Neilson Lucena; Luciana Augusto Rezende; Daniela Pereira Garçon; Marcelo Rodrigues Pinto; Fernando Luis Mantelatto; John Campbell McNamara (The Journal of Membrane Biology, 2015)

Claudin-3 and occludin tissue content in the glands of colonic mucosa with and without a fecal stream - Carlos Augusto Real Martinez; Fabio Guilherme Caserta Maryssael de Campos; Viviel Rodrigo José de Carvalho; Caroline de Castro Ferreira; Murilo Rocha Rodrigues; Daniela Tiemi Sato; José Aires Pereira (Journal of Molecular Histology, 2015)

The Interplay Between Apoptosis, Mitophagy and Mitochondrial Biogenesis Induced by Resveratrol Can Determine Activated Hepatic Stellate Cells Death or Survival - Leo A. Meira Martins; Moema Queiroz Vieira; Mariana Ilha; Mariana de Vasconcelos; Henrique B. Biehl; Daniela B. Lima; Vanessa Schein; Florencia Barbé-Tuana; Radovan Borojevic; Fátima Costa Rodrigues Guma (Cell Biochemistry and Biophysics, 2015)

Ecological literacy and beyond: Problem-based learning for future professionals - Thomas M. Lewinsohn; José Luiz Attayde; Carlos Roberto Fonseca; Gislene Ganade; Leonardo Ré Jorge; Johannes Kollmann; Gerhard E. Overbeck; Paulo Inácio Prado; Valério D. Pillar; Daniela Popp; Pedro L. B. da Rocha; Wesley Rodrigues Silva; et al. (Ambio, 2015)

Identification of familial clustering for cancer through the family health strategy program in the municipality of Angra dos Reis, Rio de Janeiro, Brazil - Daniela Koeller Rodrigues Vieira; Margareth Attianezi; Ana Carolina Esposito; Anneliese Barth; Cecília Sequeira; Nathália Krause; Vivian Oliveira; Alexandre Lucidi; Cassio Serao; Juan C. Llerena (Journal of Community Genetics, 2015)

Advanced glycation end products and diabetic nephropathy: a comparative study using diabetic and normal rats with methylglyoxal-induced glycation - Lisa Rodrigues; Paulo Matafome; Joana Crisóstomo; Daniela Santos-Silva; Cristina Sena; Paulo Pereira; Raquel Seiça (Journal of Physiology and Biochemistry, 2014)

Behavioral and life-history evidence for interspecific competition in the larvae of two heliconian butterflies - Carolina Millan; Simone Silva Borges; Daniela Rodrigues; Gilson Rudinei Pires Moreira (The Science of Nature, 2013)

Contrasting egg and larval performances help explain polyphagy in a florivorous butterfly - Daniela Rodrigues; André V. L. Freitas (Arthropod-Plant Interactions, 2013)

Synthetic Condensed 1,4-naphthoquinone Derivative Shifts Neural Stem Cell Differentiation by Regulating Redox State - Daniela M. Santos; Maria M. M. Santos; Rui Moreira; Susana Solá; Cecília M. P. Rodrigues (Molecular Neurobiology, 2013)

Resistance to Meloidogyne incognita race 1 in the lettuce cultivars Grand Rapids and Salinas-88 - José Luiz Sandes de Carvalho Filho; Luiz Antonio Augusto Gomes; Wilson Roberto Maluf; Rafael Resende Oliveira; Daniela Santos Costa; Sindynara Fereira; Aline Beraldo Monteiro; Rejane Rodrigues da Costa e Carvalho (Euphytica, 2011)

Effects of abiotic factors on growth and chemical defenses in cultivated clones of Laurencia dendroidea J. Agardh (Ceramiales, Rhodophyta) - Daniela Bueno Sudatti; Mutue Toyota Fujii; Silvana Vianna Rodrigues; Alexander Turra; Renato Crespo Pereira (Marine Biology, 2011)

Anti-inflammatory and immunomodulatory effects of RDV-8 [C18H22N2O2S (ethyl 1-butyl-6-methyl-2-phenyl-4-thioxo-1,4-dihydropyrimidine-5-carboxylate)] in a rat model of induced pleurisy and in vitro lymphoproliferation - Marcos Schuch Azambuja; Adroaldo Lunardelli; Robson Henrich Amaral; Fernanda Bordignon Nunes; Eduardo Caberlon; Vinicius Lorini da Costa; Márcio Vinícius Fagundes Donadio; Daniela Nunes Vitor; Denizar Alberto da Silva Melo; Silvio Cunha; Jarbas Rodrigues de Oliveira (Inflammopharmacology, 2011)

Variation in Nectar and Pollen Availability, Sucrose Preference, and Daily Response in the Use of Flowers by Heliconius erato phyllis - Elisete A. Barp; Geraldo L. G. Soares; Erica J. M. Giani; Daniela Rodrigues; Gilson R. P. Moreira (Journal of Insect Behavior, 2011)

Bacterial community associated with the trunk latex of Hancornia speciosa Gomes (Apocynaceae) grown in the northeast of Brazil - Thais Freitas da Silva; Marcia Reed Rodrigues Coelho; Renata Estebanez Vollú; Fátima Regina de Vasconcelos Goulart; Daniela Sales Alviano; Celuta Sales Alviano; Lucy Seldin (Antonie van Leeuwenhoek, 2011)

Purification of coagulation factor VIII using chromatographic methods. Direct chromatography of plasma in anion exchange resins - Elisabeth Cheng; Daniela Jinzenji; Ana Paula Almeida Aranha Lorthiois; Roberta Rodrigues de Carvalho; Anita Mitiko Tanaka-Azevedo; Isaías Raw; Elizabeth Angélica Leme Martins (Biotechnology Letters, 2010)

Trade-offs underlying polyphagy in a facultative ant-tended florivorous butterfly: the role of host plant quality and enemy-free space - Daniela Rodrigues; Lucas A. Kaminski; André V. L. Freitas; Paulo S. Oliveira (Oecologia, 2010)

Nitrogen aboveground turnover and soil stocks to 8 m depth in primary and selectively logged forest in southern Amazonia - TED R. FELDPAUSCH; EDUARDO G. COUTO; LUIZ CARLOS RODRIGUES; DANIELA PAULETTO; MARK S. JOHNSON; TIMOTHY J. FAHEY; JOHANNES LEHMANN; SUSAN J. RIHA (Global Change Biology, 2010)
Extensive areas of Amazonia undergo selective logging, modifying forest structure and nutrient cycles. Anthropogenic‐accelerated rates of nitrogen (N) turnover could increase N loss and affect regeneration, carbon sequestration and timber production. We quantified leaf area reduction, canopy opening and downed biomass and resultant N flux from reduced impact logging (RIL) activities. We compared canopy reduction, surface soil moisture and nitrate to 8 m depth between logged gaps and intact primary forest to determine if logging activities increase subsoil nitrate. To test long‐term logging effects, we evaluated surface N stocks along a 12‐year postlogging chronosequence. At the harvest rate of 2.6 trees ha −1 , total N additions in logging gaps, including leaves and wood from felled crowns (24.8 kg N ha −1 ) and other killed trees (41.9 kg N ha −1 ), accounted for over 80% of the total N addition to aboveground necromass from all logging activities (81.9 kg N ha −1 ). Despite this N turnover by logging, belowground nitrate storage to 8 m depth did not differ between logging gaps and primary forest at the low harvest rate and disturbance intensity of this study. Soil water depletion also did not differ between gaps and primary forest over 1 year, indicating the impact on belowground inorganic N was low. Compared with primary forest, nitrate concentrations to 8 m depth in logging gaps were only significantly higher at 60–100 cm, suggesting some N redistribution beyond the bulk of the fine roots in logging gaps. Extrapolated to the Amazon Basin scale, we provide a conservative estimate that logging damage and bole export under RIL would turn over 0.14 ± 0.07 to 0.23 ± 0.12 Tg N yr −1 based on 1999–2002 selective logging rates. Greater damage during conventional selective logging would cause higher N turnover throughout the Amazon Basin than our results based on RIL.

Leishmania amazonensis Growth Inhibitors: Biological and Theoretical Features of Sulfonamide 4-Methoxychalcone Derivatives - Alessandra M. T. Souza; Helena C. Castro; Monique A. Brito; Carla R. Andrighetti-Fröhner; Uiaran Magalhães; Kely N. Oliveira; Daniela Gaspar-Silva; Letícia K. Pacheco; Antônio C. Joussef; Mário Steindel; Cláudia M. O. Simões; Dilvani O. Santos; et al. (Current Microbiology, 2009)

Incidence and risk factors for agranulocytosis in Latin American countries—the Latin Study - Nelson Hamerschlak; Eliane Maluf; Alexandre Biasi Cavalcanti; Álvaro Avezum Júnior; José Eluf-Neto; Roberto Passeto Falcão; Irene Gyongyvér Heidemarie Lorand-Metze; Daniel Goldenberg; Cézar Leite Santana; Daniela de Oliveira Werneck Rodrigues; Leny Nascimento da Motta Passos; Erika Oliveira de Miranda Coelho; et al. (European Journal of Clinical Pharmacology, 2008)

Indirect immune detection of ecdysone receptor (EcR) during the formation of DNA puffs in Bradysia hygida (Diptera, Sciaridae) - Juliana Aparecida Candido-Silva; Daniela Palermo de Carvalho; Graciana Rodrigues Coelho; Jorge Cury de Almeida (Chromosome Research, 2008)

Quantitative GC-ECD Analysis of Halogenated Metabolites: Determination of Surface and Within-Thallus Elatol of Laurencia obtusa - Daniela Bueno Sudatti; Silvana Vianna Rodrigues; Renato Crespo Pereira (Journal of Chemical Ecology, 2006)

Differential expression of sialylglycoconjugates and sialidase activity in distinct morphological stages of Fonsecaea pedrosoi - Jos N. S. S. Couceiro; Rosangela M. A. Soares; Celuta S. Alviano; Andr L. S. Santos; Marcio L. Rodrigues; Daniela S. Alviano; Catia A. Almeida; Luiz R. Travassos (Archives of Microbiology, 2004)

Pharmacological demonstration of the differential involvement of protein kinase C isoforms in short- and long-term memory formation and retrieval of one-trial avoidance in rats - Monica R. M. Vianna; Daniela M. Barros; Tiago Silva; Humberto Choi; Cristina Madche; Cleverson Rodrigues; Jorge H. Medina; I. Izquierdo (Psychopharmacology, 2000)